Characterization and application potential of two newly isolated phages targeting the prevalent multidrug resistant Salmonella serovars in China - Mei-Jun Chu; Junjie Wang; Xiu-Lei Gu; Jianxia Li; Zhiyuan You; Kelan Yi; Hao Wang; Bao-Tao Liu (International Journal of Food Microbiology, 2026)

Physicochemical pretreatment for enhancing anammox and related coupled processes in the treatment of high-strength ammonium industrial wastewater: Research advances and prospects - Long Jiao; Xue-chao Wang; Jia-lin Xue; Zhuo-yuan You; Jie Li; Jia-jun Fu; Hong Yu (Journal of Environmental Chemical Engineering, 2026)

Bamboo charcoal meets ceramic: A novel hybrid filler BAF for enhanced nutrient removal and microbial stability under trace Cu2+ exposure - Shengnan Zhang; Yongjun You; Chaoqun Chen; Xinbo Guo; Jun Jing; Jie Wang; Chong Liu; Juanxiang Zhang; Fayong Li (Journal of Environmental Chemical Engineering, 2026)

Engineering a robust glucose oxidase: Enhanced thermostability, acid tolerance and catalytic activity drive high-level gluconic acid production - Ying-Zhi Peng; Xin-Cheng Jiang; Jing Li; Yi-Fa Yu; Jia-Yu He; Bing-Yan Xu; Xiang Lv; Qiong-Ying Wu; Shuai You; Jun Wang (Food Chemistry, 2026)

Salinity-induced dynamics of antibiotic resistance genes across size-fractionated lifestyles: Microbial community coalescence revealed by a comprehensive source–sink framework - Guoxiang You; Chengxing Huang; Yongheng Deng; Mengting Li; Yanhong Xia; Yi Xu; Jun Hou (Environmental Pollution, 2026)

Mechanism exploration of divergent partial denitrification performance under tetracycline stress: Insights from functional gene, electron transport and molecular docking - Biao Li; Yufei You; Yajun Fan; Jun Wu; Xiaofan Lv; Junjie Ji; Miao Zhang (Journal of Hazardous Materials, 2026)

Dual-site ionized covalent organic frameworks with enhanced charge density for highly efficient and selective adsorption of 99TcO4-/ReO4- - Meng Li; Shiyuan Wei; Hao Wang; Jun Cao; Jiawei Li; Jianhan Huang; You-Nian Liu (Journal of Hazardous Materials, 2026)

N'-(4-fluorophenyl)-2-pyridinecarbohydrazide targets succinate dehydrogenase to control citrus blue mold - Liangliang Gao; Tengjie Li; Zengrong Xiang; Mingnan You; Jun Zhang; Nengguo Tao (Food Microbiology, 2026)

Mechanisms of aerobic simultaneous nitrogen removal under low COD/N conditions: Diffusion–reaction coupling and particle size effects via self-recirculating microgranular system - Lifang Liu; Cong Wang; Wei-Kang Qi; Shu-Jun Zhang; Yu-You Li; Yongzhen Peng (Water Research, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Hydro/photo-responsive multicolor luminescence switching in a europium-functionalized HOF for information anticounterfeiting - Jun Wang; Huaxue Xu; Wei Ren; Xinyue Li; You Zhou; Bing Yan (Chemical Engineering Journal, 2026)

Pesticide beta-cypermethrin impairs endometrial decidualization and embryo implantation by suppressing autophagy through oxidative stress - Li-Qing Wang; Huang-Nian You; Qiong-Jun Xu; Wen-Jie Yu; Xiao-Mei Wu; Xiao-Qing Pang; Xiao-Xi Chen; Wen-Bin Du; Qian-Feng Qiao; Jing-Ai Li; Yu-Meng Zhou; Yong-Jiang Zhou (Chemico-Biological Interactions, 2026)

Shear performance of prefabricated utility tunnel joints considering the effect of connectors - Chao Zhang; Jiao-jiao Chen; Wei-ning Zhong; Xin Li; Chen-chen Sun; You-jun Xu; Xin Han; Jun-yi Gao; Jian-jun Wang; Zhi-qiang Fu (Tunnelling and Underground Space Technology, 2026)

Effect of ether oxygen atom distribution in the polymer main and side chains on the lithium-ion conductivity of PEG-based polymer electrolytes - Zhiyu Chen; Hao Lei; Zhaoyang Wei; Weiwei Lei; Ke Wang; Jun You; Qunchao Zhang; Robert K.Y. Li; Ming Zhou; Qiang Yuan; Dean Shi (Chemical Engineering Journal, 2026)

Low-barrier interface via noble metal induction for external energy-free ppb-level room-temperature formaldehyde sensing - Ziming Yang; Jiangnan Chang; Ying Qiao; Sitao Lv; Leqi Zhang; Yifei Fan; You Wu; Ruofei Lu; Hao Li; Yanan Guo; Patrick J. French; Jun Yin; et al. (Chemical Engineering Journal, 2026)

Exploring gut microbiota responses to low-dose thallium exposure via food chain transfer: insights from soil–plant–human systems - Lu-Xiu Lin; Wei-Jun Chen; Shun-Xing Li; Feng-Ying Zheng; Xu-Guang Huang; Feng-Jiao Liu; Jia-Yi Luo; Zhao-Jing Huang; Wen-Jie Zhang; You-Bin Zhuo; Xin Long (Environmental Geochemistry and Health, 2026)

Innovative PANI composite modified conductive FO membranes for electro-assisted aquaculture wastewater recovery - Yi-Li Lin; Nai-Yun Zheng; Jun-You Lin; Ngoc Hong Nguyen (Journal of Water Process Engineering, 2026)

Corrigendum to “Effects of vacuum steam pulsed blanching on bioactive compounds, quality attributes, enzyme activities, and microstructural properties of daylily (Hemerocallis citrina Baroni)” [Food Chem. 506 (2026) 148147] - Jun Zhang; Li-Zheng Deng; Wei-Peng Zhang; Ming-Qiang Xu; You-Sheng Shi; Shi-Han Yu; Jing-Shou Zhang; Fan Yang; Shu-Lin Liu; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Five new prenylated flavonoids derivatives from Dysosma versipellis and their DPPH radical scavenging activity - Meng Zhang; Hong-Yun Bai; Ling-Yu Ye; Xiao-Ke Zheng; Meng Li; Hui Chen; Jing-Ke Zhang; Zhi-You Hao; Shen Liang; Yan-Jun Sun; Wei-Sheng Feng (Phytochemistry Letters, 2026)

Cissatriterpenoids D-L, nine undescribed polyhydroxylated oleanane triterpenoids from Cissampelos pareira var. hirsuta - Shuang-Qin Cao; Ru-Yi Pan; Tong-Tong Zhang; Jian-Hong Gong; Meng Li; Hui Chen; Jing-Ke Zhang; Zhi-You Hao; Xiao-Ke Zheng; Yan-Jun Sun; Wei-Sheng Feng (Phytochemistry, 2026)

Impacts of antibiotics on anammox performance and exploration of mitigation strategies for wastewater treatment: A critical review - Biao Li; Yufei You; Yajun Fan; Jun Wu; Miao Zhang (Journal of Water Process Engineering, 2026)

Insights into antibiotic resistance gene dynamics during Tanfloc-induced flocculation-storage process for cyanobacteria removal in an algae-laden drinking water source - Guoxiang You; Haoyan Jin; Miao Wu; Yongnian Li; Xiuzhou You; Chengxing Huang; Yi Xu; Jun Hou (Journal of Environmental Management, 2026)

Functional division of labor within defined yeast consortia drives flavor formation during early solid-state fermentation of sichuan shai vinegar - Jiajie Zhu; Yuting Liao; Yulin Zhao; Jun Liu; Zhicheng Li; Xiangpeng Kong; Suyi Zhang; Chuan Song; Qixu Fu; Xianbin Wang; Ruiqi Xue; Xuemei Shi; et al. (Food Microbiology, 2026)

Prevalence and genomic characterization of pathogenic blaNDM-positive Escherichia coli from retail meats: The first large-scale study in 22 cities of China - Mei-Jun Chu; Ming Zou; Han Wang; Junjie Wang; Zhiyuan You; Yan Li; Bao-Tao Liu (Food Microbiology, 2026)

β-Glucanase engineering oriented to industrial biorefinery: Database-based directed evolution for thermostability optimization - Xiao-Lu Zhu; Shu-Biao Yuan; Jing Li; Marriam Khurshid; Richard Ansah Herman; Jie Qi; Hong-Yu Guo; Wei-Guo Zhao; Jun Wang; Shuai You (Biomass and Bioenergy, 2026)

Classification and Evaluation of a Shale Oil Reservoir in the Qingshankou Formation in the Southern Songliao Basin, NE China - Guofeng Wang; Dawei Zhang; Liang Yang; Yongqing Zhang; Junling He; Jilin Xing; Jun Jiang; Jijun Li; Shuning Zhang; Chenxu Yan; Hang You; Ketao Zheng; et al. (Journal of Earth Science, 2026)

Effects of vacuum steam pulsed blanching on bioactive compounds, quality attributes, enzyme activities, and microstructural properties of daylily (Hemerocallis lilioasphodelus L.) - Jun Zhang; Li-Zheng Deng; Wei-Peng Zhang; Ming-Qiang Xu; You-Sheng Shi; Shi-Han Yu; Jing-Shou Zhang; Fan Yang; Shu-Lin Liu; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Cereal-legume intercropping stabilizes yield and economic advantages under variable rainfall in semiarid rainfed environment - Wei Wang; Bao-Zhong Wang; Wei Zhang; Meng-Ying Li; Jian-Ming Li; Sheng-Jun Ji; Muhammad Abrar; Muhammad Maqsood Ur Rehman; Wasim Khan; Hong-Yan Tao; Mohamed S. Sheteiwy; Wen-Ying Wang; et al. (European Journal of Agronomy, 2026)

Promoting the ionic conductivity and self-healing ability of micro-Si anode via a versatile crosslinker of Al(H2PO4)3 - Yang-Ning You; Shu-Hao Guo; Tao Li; Yu-Jun Bai; Xi-Cheng Ma (Chemical Engineering Journal, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Large-scale cultivation of Haliclona simulans sponge larvae on soft substrates and the enhancing effect of Chlorella - Zhunfei Li; Ming Chen; Yingzhe You; Jun Chen (Aquaculture, 2026)

DEHP induces hepatic fibrosis through STAT3-SLC7A11-ROS axis - Siqin Liang; Zhiliang Xu; Xiaoxiang You; Tinghao Yuan; Jun He; Lei Mao; Anan Jin; Xinwen Zhou; Bo Yi; Ming Li; Qiang Tu; Bin Xu (Toxicology and Applied Pharmacology, 2026)

Antioxidant activity and emulsifying properties of Dendrobium officinale polysaccharides with distinct structural characteristics - Cunchao Zhao; Weiqian Wang; Fanrui Li; Jun Sheng; Rui He; Lijun You; Yang Tian (Food Chemistry, 2026)

Targeted degradation of emerging pollutants based on specific recognition and ROS confinement effects of molecularly imprinted cavities - Jun Bo Zhang; Xu Jiang; Chaomeng Dai; Jixiang Li; Jiajun Hu; Min-tian Gao; Xueji You; Hongcheng Zhang; Shunyang Li; Peng Qiu; Zhu Zhu; Xihua Wang; et al. (Chemical Engineering Journal, 2026)

Predicting cyanobacteria removal efficiency in flocculation-DAF: Improving interpretable automated machine learning with CVAE data augmentation - Xiao Zhao; Zijun Yang; Jianjian Wei; Zixuan Wang; Cheng Cheng; Wanyi Li; Jihang Li; Yutong Zhang; You Zuo; Jun Hou (Water Research, 2026)

Computer vision-assisted sorting and selective cultivation of high-activity anammox granules - Shi-Jun Li; Haoran Li; Hui-Min Fu; Yi-Cheng Wang; Xun Weng; Wei Wang; You-Peng Chen (Water Research, 2026)

Long-term intercropping mitigates warming-induced carbon loss via enhancing microbial and substrate resistance - Wei Wang; Yang Wang; Jian-Ming Li; Meng-Ying Li; Peng He; Yongxing Cui; Sheng-Jun Ji; Wen-Ying Wang; Levis Kavagi; Muhammd Ashraf; Yinglong Chen; Matthias C. Rillig; et al. (Soil Biology and Biochemistry, 2026)

Composite lixiviant synergy for ionic rare earth extraction: Dual-perspective mechanistic insights from metabolomics and mineralogical characterization - Yaru Duan; Lingyan Li; Jiale You; Haitao Wang; Yun Fang; Jun Wang; Yang Liu; Ruan Chi; Chunqiao Xiao (Minerals Engineering, 2025)

Cradle-to-gate carbon footprint of industrial-scale fermentative production of poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (PHBH) - Hsien-Tse Chen; Yu-Hsiang He; Pei-Yi Lin; Wei-Shu Huang; Kaarmukhilnilavan R. Srinivasan; Jun-You You; Pei-Yu Sun; Allen H. Hu; Penjit Srinophakun; Maythee Saisriyoot; Si-Yu Li (Journal of Cleaner Production, 2025)

Low-temperature soda-ash roasting of ludwigite ore: Scale-up feasibility for magnetite and borax production - Jinxiang You; Xin Zhang; Mingjun Rao; Jun Luo; Zhiwei Peng; Guanghui Li (Journal of Environmental Chemical Engineering, 2025)

Regulation of vascular smooth muscle cells phenotype by metformin up-regulated miR-1/ CCND1 axis via targeting AMPK/TGF-β signaling pathway - Yulin Luo; Mengting Li; Jingcan You; Jun Jiang; Min Zeng; Mao Luo (Molecular Biology Reports, 2025)

Satb2 Ablation Impairs Hippocampus-Based Long-Term Spatial Memory and Short-Term Working Memory and Immediate Early Genes (IEGs)-Mediated Hippocampal Synaptic Plasticity - Ying Li; Qiang-Long You; Sheng-Rong Zhang; Wei-Yuan Huang; Wen-Jun Zou; Wei Jie; Shu-Ji Li; Ji-Hong Liu; Chuang-Ye Lv; Jin Cong; Yu-Ying Hu; Tian-Ming Gao; et al. (Molecular Neurobiology, 2025)

Impact of Foliar Application of Zinc Sulphate with Nitrogen Fertilizer on Morphological Responses and Yield Improvement of Winter Wheat (Triticum aestivum L.) - Riaz Ahmed; Junyi Mu; Jun Xing; Mehr Un Nisa; Yulai Zhang; Pengcheng Ding; Linghong Li; Ying You; Aixia Ren; Zhiqiang Gao; Min Sun (International Journal of Plant Production, 2025)

Visible-light driven synergistic adsorption-photocatalysis by S-scheme CoTiO3@Cu-BDC-NH2 MOF photocatalyst for tetracycline and chromium removal - Soodamani Periyasamy; Jun Hou; Yang Li; Natrayasamy Viswanathan; Zijun Yang; Guoxiang You; Jun Wu; Zhaoqin Huang (Journal of Environmental Management, 2025)

Polystyrene nanoplastics impair endometrial decidualization via cell cycle arrest and JNK-MAPK pathway-mediated oxidative stress in early pregnant mice - Jing-Ai Li; Li-Qing Wang; Qiong-Jun Xu; Xiao-Mei Wu; Xiao-Qing Pang; Jin-Xin He; Qian-Feng Qiao; Huang-Nian You; Yan-Chun Wu; Yong-Jiang Zhou (Food and Chemical Toxicology, 2025)

Crushing characteristics and energy dissipation modeling of Single-Particle-Size carbonaceous mudstone as roadbed fill - Yan Wang; Hong-yuan Fu; Jian-Ping Song; Ling Zeng; Tao Li; Jian-Ping Xiong; Hong-Ri Zhang; Wen-Guang Wang; You-Jun Li; Jing-Cheng Chen (Bulletin of Engineering Geology and the Environment, 2025)

Phylogenomic insights into historical biogeography and species delimitation of African Ampelocissus (Vitaceae) - Romer Narindra Rabarijaona; Jin-Ren Yu; Zhi-Yong Tang; Rindra Manasoa Ranaivoson; Russell L. Barrett; Mijoro Rakotoarinivo; Bing Liu; Yi-Chen You; Samaila S. Yaradua; Romeo Gbiribou; Jun Wen; Zhi-Duan Chen; et al. (Molecular Phylogenetics and Evolution, 2025)

Efficient activation of percarbonate by metal-free carbonylated activated carbon for green groundwater remediation: Performance, mechanism, applicability, and environmental implications - Jun Bo Zhang; Yi Yang; Chaomeng Dai; Jixiang Li; Yucang Liang; Jiajun Hu; Min-tian Gao; Xueji You; Xu Jiang; Shunyang Li; Xihua Wang; Zhi Li; et al. (Journal of Hazardous Materials, 2025)

A Typical Riedel Shear Pattern of Active Faults in the Laolongwan Basin, Northeastern Tibetan Plateau - Kai-Xun Wang; Xiao-Gang Li; Wei Shi; Xiang-You Feng; Qian Yang; Jie Li; Zheng-Jian Xu; Zhou-Jun Peng; Shao-Hua Xu; Yi-Xue Xiong; Mao Lin (Journal of Earth Science, 2025)

Removal of emerging organic contaminants in a subsurface wastewater infiltration system: A preliminary study of microbial mechanism - Feng-Jiao Peng; Xing-Jun Feng; Sen Li; Xiao-Long Yu; Jun Chen; Shuang-Shuang Liu; Guang-Guo Ying; You-Sheng Liu (Water Research, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Discovery of undescribed schinortriterpenoids from Schisandra chinensis by molecular networking and their neuroprotective effects - Peng Jiang; Yu-Meng Luo; Xin-Yuan Li; Shu-Jun Zhang; Wei Guan; Anam-Naseem; Yu-Hang Fan; Qing-Shan Chen; Li-Li Zhang; Hong-Yan Yao; Xiao-Xue He; Hai-Xue Kuang; et al. (Phytochemistry, 2025)

Reducing environment and enhanced productivity controlled the accumulation of organic matter in the Upper Yangtze Basin, South China during the Late Ordovician-Early Silurian - Yan-Jun Bao; Yuan-Yuan Sun; Di Zhang; Jian-Fei Yan; Yu-Peng Men; Wei Sun; Jia-Shan Lin; You-Li Wan; Jian-Wei Kang; Wen-Hua Wang; Qiangba Zhaxi (Journal of Asian Earth Sciences, 2025)

Unlocking bio-H2 production potential from straw–sludge co-substrates: The role of Fe/Mn-biochar in alleviating carbon catabolite repression - Ji-wen Wu; Shi-jie You; Chun-shuang Zhou; Qi Xi; Jia-ning Fan; Jun Ma; Guang-li Cao (Chemical Engineering Journal, 2025)

Microbial nutrient limitations and chemical composition of soil organic carbon regulate the organic carbon mineralization and temperature sensitivity in forest and grassland soils - Mengyang You; Diankun Guo; Hongai Shi; Peng He; Martin Burger; Lu-Jun Li (Plant and Soil, 2025)

A novel graphene oxide functionalized hydrocalumite/cellulose composite for the selective and simultaneous removal of tetracycline and Cr(VI) - Soodamani Periyasamy; Jun Hou; Natrayasamy Visawanathan; Yang Li; Zijun Yang; Guoxiang You (Environmental Research, 2025)

Parapedobacter flavus sp. nov., isolated from padding of fermentation bed - Rui Wang; Yan-Yan Zheng; Zi-Xuan Liu; Xuan Zhang; You-Jun Liao; Ya-Jing Yu; Ai-Hua Li (Antonie van Leeuwenhoek, 2025)

Visual Detection of Cadmium and Glutathione by Dicyanoisophorone Fluorescent Probe and its Portable Application - Panru Zu; Yanchao Yu; Bolin Li; Jun You; Wenju Wu; Mianyuan Wu (Journal of Fluorescence, 2025)

Meroterpenoids with bicyclic polyprenylated acylphloroglucinol scaffold and anti-inflammatory activity from Hypericum lancasteri - Jin-Qiu You; Yun-Qi Jin; Yu-Meng Miao; Xin-Yu Sun; Jia-Yu Yang; Jin-Chang Huang; Jing-Ya Li; Ai-Jun Hou (Phytochemistry, 2025)

Emerging contaminants in Taihu lake Basin: Multi-dimensional prioritization, colloidal adsorption, and trophic-level disruptions - Huijin Cao; Jianchao Liu; Wei You; Guanghua Lu; Yiping Li; Jun Hou; Peng Gao (Journal of Environmental Management, 2025)

Development and Application of Blasting Vibration Prediction Model - Hongchao Li; Haoxuan Han; Shenglin Li; Greg You; Jun Fu; Zhengrong Li; Xiyao Wang (Rock Mechanics and Rock Engineering, 2025)

Hydrological changes in the East Asian monsoon region around 4.2 ka precisely reconstructed from multi-proxy stalagmites - Chao-Jun Chen; Yao Wu; Jun-Yun Li; Hai-Wei Zhang; Hai Cheng; Chuan-Chou Shen; You-Feng Ning; Dao-Xian Yuan; R. Lawrence Edwards; Jian Zhang; Ting-Yong Li (Quaternary Science Reviews, 2025)

Strengthening mechanism of water content reduction in electrolytic manganese residue by sodium oleate - Jing Wang; Zihan Li; Jiancheng Shu; Zongchen Wei; Shaoqin Chen; Hongyuan Zhao; Jun Luo; Huimin Yang; Yanyan You; Mengjun Chen; Yong Yang (Journal of Environmental Chemical Engineering, 2025)

Effects of semipermeable membrane-covered composting on greenhouse gas mitigation and microbiome at different ambient temperatures at an industrial scale - Junwei Yuan; Siyuan Lin; Yi Wang; Wenxiang He; Yangyang Li; Junda Wu; Liang Cai; Xiaoyan Kong; Dongqi You; Bo Liu; Jun Hou (Journal of Environmental Chemical Engineering, 2025)

East Asian dust storm in March 2021: Perspective views from ground observation, satellite measurement and numerical simulation - Yi-Bo Xue; Xiao-Xiao Zhang; Jia-Qiang Lei; Sheng-Yu Li; Lian-You Liu; Zi-Fa Wang; Wen-Jun Tian; Xiao Tang; Xue-Shun Chen (Atmospheric Environment, 2025)

Cascading environmental, phenological, and physiological influences on spatial variability of annual gross primary productivity in the Northern Hemisphere - Lang Han; Gui-Rui Yu; Zhi Chen; Qiu-Feng Wang; Xian-Jin Zhu; Wei-Kang Zhang; Tie-Jun Wang; Zhi-Feng Yan; Tian-You Zhang; Shi-Ping Chen; Hui-Min Wang; Jun-Hua Yan; et al. (Science of The Total Environment, 2025)

Exploring the role of dipole moment at the upper interface of inverted perovskite solar cells through a bi-molecular host–guest strategy - Guoqiang Xu; Imran Muhammad; Danish Khan; Xiaojian Zheng; Yu Zhang; Min Xin; Huaxi Gao; Jiahao Li; Junyu Wang; Di Lu; Shehzad Ahmed; Peng You; et al. (Chemical Engineering Journal, 2025)

Stalagmite multi-proxy records reveal spatial complexity of precipitation and monsoon variability in China over past 60 years - Yan-Xia Xue; Yao Wu; Chao-Jun Chen; Tao Fan; Huai Su; Han-Ying Li; Hai Cheng; Jian-Jun Yin; Jun-Yun Li; You-Feng Ning; Ting-Yong Li (Quaternary Science Reviews, 2025)

Denitrification enhancement, kinetic simulation and microbial assessment in the sponge iron-mediated anammox process: A method for low-strength nitrogen wastewater treatment - Miao Zhang; Zhongkuo Guan; Biao Li; Yufei You; Guihua Cao; Yajun Fan; Jun Wu; Junjie Ji (Journal of Water Process Engineering, 2025)

Biomimetic mineralization materials for heterogeneous chemo-enzymatic cascade catalytic systems: Theaters and players - Mengyu Li; Fenfen You; Keke Zhang; Jingliang Xu; Wei Zhuang; Jun Ge; Zhenfu Wang (Chemical Engineering Journal, 2025)

Unraveling microbial community ecology and its effects on function and structure of halophilic aerobic granular sludge under varying salinities - Hui-Juan Yan; You-Wei Cui; Jun Chen; Hui-Kai Liang; Zhen-Ying Li (Bioresource Technology, 2025)

Elucidation of the stress mechanisms on activated sludge stability induced by yttrium oxide nanoparticles with cytotoxicity: Performance deterioration, biointerface variation and microbial response - Shen Cui; Lei Yang; Haoqi Lu; Linkai Guo; Yuchao Wang; Jun Lan; Yong-Xiang Ren; Yu-You Li (Bioresource Technology, 2025)

Neural Stem Cell Extracellular Vesicles Carrying YBX1 Inhibited Neuronal Pyroptosis Through Increasing m6A-modified GPR30 Stability and Expression in Ischemic Stroke - Jun Peng; Jun He; Long Lin; You Li; Ying Xia (Translational Stroke Research, 2025)

Transcriptome Profiling of Mutant iew-1 with Epicuticular wax Increase in Common Wheat (Triticum aestivum L.) - Tong Gou; Qiqi Ha; Jun Xing; Xiaoting Xie; Aixia Ren; Pengcheng Ding; Ying You; Zhiqiang Gao; Feng Liu; Linghong Li; Min Sun (Journal of Plant Biology, 2025)

Exploring the physical disruptions of anammox granular sludge under propylene glycol stress: Implications for nitrogen removal and long-term stability - Hui-Min Fu; Xiao-Wen Jiang; Cai-Ping Sun; Shi-Jun Li; Xun Weng; Meng-Wen Peng; Peng Yan; Xiao-Wei Xu; You-Peng Chen; Yu Shen (Journal of Water Process Engineering, 2025)

Toxicity assessment of wastewater using a battery of bioassays in two textile wastewater treatment plants from a large industrial park in Guangxi, Southwest China - Feng-Jiao Peng; Sen Li; Wen-Dan You; Xin-Yu Wang; Xing-Jun Feng; Bin Yang; Guang-Guo Ying (Science of The Total Environment, 2025)

Revealing microbial compatibility of partial nitritation/Anammox biofilm from sidestream to mainstream applications: Origins, dynamics, and interrelationships - Yanxiao Wei; Weizhe Xia; Yunzhi Qian; Chao Rong; Min Ye; Yujie Chen; Jun Kikuchi; Yu-You Li (Bioresource Technology, 2025)

Shelterbelt influence on soil microbial carbon and phosphorus limitation in farmland: Implications for soil health - Peng He; Xuechen Yang; Zhiming Zhang; Shan-Shan Dai; Mengyang You; William R. Horwath; Peng Zhang; Wenjie Wang; Lu-Jun Li (Agriculture, Ecosystems & Environment, 2025)

Study on excitation effect of different combination modes of shear wave vibroseis - Zhengtao You; Zhiqiang Huang; Lei Hao; Gang Li; Mingwei Fu; Ruohao Wang; Jun Shuai (Acta Geophysica, 2025)

Global occurrence, food web transfer, and human health risks of polycyclic aromatic hydrocarbons in biota - Jingqian Xie; Ruo Lan; Li Zhang; Jun Yu; Xinran Liu; Zhiyang You; Fen Yang; Tian Lin (Science of The Total Environment, 2025)

Unraveling the resistance mechanism of anammox granular sludge to iron nanoparticles - Xun Weng; Meng-Jiao Gao; Zheng Mao; Hui-Min Fu; Shi-Jun Li; Peng Yan; You-Peng Chen (Journal of Environmental Management, 2025)

Effects of reduced flow gradient on benthic biofilm communities’ ecological network and community assembly - Lingzhan Miao; Weiyu Li; Chaoran Li; Tanveer M. Adyel; Guoxiang You; Yi Xu; Jun Wu; Yu Yao; Ming Kong; Jingjie Feng; Jun Hou (Environmental Research, 2025)

Dual regulation of structure and interface enabled high-rate and high-capacity hard carbon anode for sodium-ion batteries - Chengfan Jiang; Yue Li; Chao Wan; Qing Wu; Song Yang; Kui Chen; Yang You; Yaozhu Tian; Jun Huang; Haibo Xie (Chemical Engineering Journal, 2025)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Distinct effects of flow intermittency on the benthic microbial diversity and their denitrification on different substrates - Lingzhan Miao; Junling Zhang; Dan Luo; Tanveer M. Adyel; Yanhui Ao; Chaoran Li; Yu Yao; Jun Wu; Guoxiang You; Jun Hou (Science of The Total Environment, 2024)

Optimizing ABA-based chemically induced proximity for enhanced intracellular transcriptional activation and modification response to ABA - Zeng Zhou; Yue-Qi Wang; Xu-Nan Zheng; Xiao-Hong Zhang; Lu-Yao Ji; Jun-You Han; Ze-Cheng Zuo; Wei-Liang Mo; Li Zhang (Science China Life Sciences, 2024)

Unraveling the effect of electricity price on electric vehicle charging behavior: A case study in Shenzhen, China - Haoxuan Kuang; Xinyu Zhang; Haohao Qu; Linlin You; Rui Zhu; Jun Li (Sustainable Cities and Society, 2024)

Integrated induction of silver resistance determinants and production of extracellular polymeric substances in Cupriavidus metallidurans BS1 in response to silver ions and silver nanoparticles - Jia-Xin Dai; Yanshuang Yu; Le-Xing You; Hong-Lin Zhong; Yuan-Ping Li; Ai-Jun Wang; Jon Chorover; Ren-Wei Feng; Hend A. Alwathnani; Martin Herzberg; Christopher Rensing (Chemosphere, 2024)

The OsSRO1c-OsDREB2B complex undergoes protein phase transition to enhance cold tolerance in rice - Dan Hu; Yilong Yao; Yan Lv; Jun You; Yu Zhang; Qingya Lv; Jiawei Li; Stephanie Hutin; Haiyan Xiong; Chloe Zubieta; Xuelei Lai; Lizhong Xiong (Molecular Plant, 2024)

Theoretical analysis of naproxen reaction with sulfate and hydroxyl radicals in the aqueous phase: Investigating reactive sites and reaction kinetics - Ji-Feng Yang; Wan-Li You; Deng You; Li-Ying Zheng; Jun-Ling Jin; Sheng-Lian Luo (Chemosphere, 2024)

Spatial variation, emissions, transport, and risk assessment of organophosphate esters in two large petrochemical complexes in southern China - Wen-Qing Mo; Zhen-Shan Huang; Qi-Qi Li; Jun Yao; Chun-You Zhu; Hui-Ying Guo; Yuan Zeng; She-Jun Chen (Journal of Environmental Management, 2024)

Protective effects of the secondary metabolites from Quercus salicina Blume against gentamicin-induced nephrotoxicity in zebrafish (Danio rerio) model - Shuang-Hui Yin; Wen-Jun Zhang; Lu-Lu Jiang; Guang-Yue Wang; You-Jin Jeon; Yuling Ding; Yong Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Cellulose nanocrystals built multiscale hydrogel electrolyte for highly reversible all-flexible zinc ion batteries - Yue Li; Song Yang; Yang You; Yunqi Li; Yanhui Zhang; Qing Wu; Shizhao Li; Qinqin Xu; Jun Huang; Haibo Xie (Chemical Engineering Journal, 2024)

Clean and efficient process for the recycling of all components from waste printed circuit boards: Pre-treatment, bio-metallurgy, and deep utilization - Chun-chen Nie; Xi-guang Li; Qian-yun Sun; Qiang Gao; Xiang-nan Zhu; Xian-jun Lyu; Lin Li; Xiao-fang You (Journal of Cleaner Production, 2024)

Analysis of proteomics and in silico allergenicity prediction of soluble proteins in selenium-enriched peanut leaves - Qi Gao; Wei-Xuan Li; Zi-Heng Liu; Mei Tie; Xue-Jun Gu; Masaru Tanokura; You-Lin Xue (Food and Bioproducts Processing, 2024)

Pressure-triggered intense natural white emission via controllable distortions of antimony chloride dimers - Zhaojiang You; Bin Xu; Xinmiao Meng; Min Wu; Aisen Li; Lei Li; Jun Chen; Qian Li; Kai Wang (Chemical Engineering Journal, 2024)

Effects of silvopastoral systems on soil nutrient properties in the low hilly area of western Henan province, China - Peisong Liu; Fan Cheng; Jun Hu; Meng Li; Xinlong Wang; Shirong You; Weishuang Tong; Liping Cheng; Jinping Zhang; Lixuan Kou (Agroforestry Systems, 2024)

Two new alkaloids from the endophytic fungus Schizophyllum sp. HM230 isolated from Vincetoxicum mongolicum Maxim - Zhuang Li; Bing-Wen Zhang; Li Jiang; He Wang; Qing-Yun Ma; Hong-Fei Wang; Jun Zhang; Feng-Li Chen; You-Xing Zhao; Du-Qiang Luo (Natural Product Research, 2024)

Nanobubbles improve peroxymonosulfate-based advanced oxidation: High efficiency, low toxicity/cost, and novel collaborative mechanism - Jun Bo Zhang; Jia Jie Zou; Chaomeng Dai; Jiajun Hu; Xueji You; Min-tian Gao; Jixiang Li; Rongbing Fu; Yalei Zhang; Kah Hon Leong; Xing Song Xu (Journal of Hazardous Materials, 2024)

Impact of supercooling storage on physical and chemical properties of yellowfin tuna (Thunnus albacares) - Dongyoung Lee; Youngsang You; Kacie K.H.Y. Ho; Yong Li; Soojin Jun (Journal of Food Engineering, 2024)

Construction of blackberry polysaccharide nano-selenium particles: Structure features and regulation effects of glucose/lipid metabolism in HepG2 cells - Dou Zu-Man; Zhang Yu-Long; Tang Chun-Yang; Liu Chuang; Fang Jia-Qin; Huang Qiang; Chen Chun; You Li-Jun; Tan Chin-Ping; Niu Hui; Fu Xiong (Food Research International, 2024)

Amplifying enantioselectivity in asymmetric transformations using heterogeneous chiral single-rhodium-site catalyst with sustained catalytic activity - Junwen Wang; Feng Liang; Junrong Huang; Jun Li; Jingyuan Liao; Chengyao Zhao; Hengzhi You; Tao Tu; Fen-Er Chen (Chemical Engineering Journal, 2024)

Identification of UDP-glucuronosyltransferase (UGT) isoforms involved in the metabolism of Chlorophenols (CPs) - Kai Yang; Ruo-Yong Jia; Xiao-Song Li; Shao-You Lu; Jian-Jun Liu; Zhi-Peng Zhang; Zhong-Ze Fang (Chemosphere, 2024)

Polypeptide urea increases rice yield and nitrogen use efficiency through root growth improvement - Shuang Liao; Fei Deng; Wei Zhou; Li Wang; Wu Li; Hui Hu; Shi-lin Pu; Shu-xian Li; Yong Chen; You-feng Tao; Chi Zhang; Qiu-ping Li; et al. (Field Crops Research, 2024)

Short-time potentiostatic assisted borate to induce the generation of ultrathin NiFe LDH active phase for industrial-level water oxidation - Yu Ma; Jia-Jun Wang; Xiao-Han Liu; Na Xu; Xin Li; You-He Wang; Lian-Ming Zhao; Yong-Ming Chai; Bin Dong (Chemical Engineering Journal, 2024)

Superhydrophobic stretchable conductive composite textile with weft-knitted structure for excellent electromagnetic interference shielding and Joule heating performance - Tai-Bao Yang; Ji-You Zong; De-Zhuang Jia; Ling Xu; Yue-Yi Wang; Li-Chuan Jia; Ding-Xiang Yan; Jun Lei; Zhong-Ming Li (Chemical Engineering Journal, 2024)

A Four Amino Acid Metabolism-Associated Genes (AMGs) Signature for Predicting Overall Survival Outcomes and Immunotherapeutic Efficacy in Hepatocellular Carcinoma - Lu-sheng Liao; Zi-jun Xiao; Jun-li Wang; Ting-jun Liu; Feng-die Huang; Yan-ping Zhong; Xin Zhang; Ke-heng Chen; Run-lei Du; Ming-you Dong (Biochemical Genetics, 2024)

Material and microbial perspectives on understanding the role of biochar in mitigating ammonia inhibition during anaerobic digestion - Zhi-Jun Zhao; Xiao-Li Liu; Yi-Xuan Wang; Yan-Shan Wang; Jin-You Shen; Zhi-Cheng Pan; Yang Mu (Water Research, 2024)

Investigation of radiative characteristics in the near field for shear, vertical and torsional vibroseis source - Zhiqiang Huang; Jun Shuai; Lei Hao; Gang Li; Ruohao Wang; Zhengtao You; Qiaomu Wang (Soil Dynamics and Earthquake Engineering, 2024)

Mitochondria immobilized carbonized polymer dots for ratio-metric tracking mitophagy - Xueting Luo; Wentao Xiang; Yi Lu; Erjing Wang; Jun You; Cao Li; Ziqiang Xu (Chemical Engineering Journal, 2024)

ECM-inspired calcium/zinc laden cellulose scaffold for enhanced bone regeneration - Chuan Luo; Yuan-Min Li; Kai Jiang; Kai Wang; Maja Kuzmanović; Xuan-He You; Yao Zhang; Jun Lei; Shi-Shu Huang; Jia-Zhuang Xu (Carbohydrate Polymers, 2024)

Halogenated aliphatic and phenolic disinfection byproducts in chlorinated and chloraminated dairy wastewater: Occurrence and ecological risk evaluation - You-Wei Jiang; Gui-Jing Wang; Shuang Zang; Yue Qiao; Hong-Fei Tao; Qiao Li; Han Zhang; Xian-Shi Wang; Jun Ma (Journal of Hazardous Materials, 2024)

Introduction of soybean into maize field reduces N2O emission intensity via optimizing nitrogen source utilization - Wei Zhang; Jun-Sheng Lu; Ju Bai; Aziz Khan; Shu-Tong Liu; Ling Zhao; Wei Wang; Shuang-Guo Zhu; Xiao-Gang Li; Xiao-Hong Tian; Shi-Qing Li; You-Cai Xiong (Journal of Cleaner Production, 2024)

Engineering the reductive tricarboxylic acid pathway in Aureobasidium pullulans for enhanced biosynthesis of poly-L-malic acid - Zhen Qin; Jun Feng; You Li; Yin Zheng; Curtis Moore; Shang-Tian Yang (Bioresource Technology, 2024)

Phase transformations and microstructure evolution of boron-containing iron concentrate during roasting under CO-CO2-N2 atmosphere: Synergistic effect of soda-ash and CO concentration - Jinxiang You; Meishi Hu; Mingjun Rao; Xin Zhang; Jun Luo; Zhiwei Peng; Guanghui Li (Minerals Engineering, 2024)

Simultaneous enhanced generation of reactive oxygen species and H2 over Pd-(Cu-s-Fe0) trimetal for bifunctional catalytic degradation of refractory combined pollutants - Jing Yang; Yongming Ju; Fangfang Li; Shibo Yan; Yu Gong; Zhiyi Deng; Yan You; Jun Luo; Shengtian Zhang (Journal of Cleaner Production, 2024)

Targeted degradation of naphthalene by peroxymonosulfate activation using molecularly imprinted biochar - Xueji You; Chaomeng Dai; Zeyu Wang; Yanping Duan; Jun Bo Zhang; Xiaoying Lai; Jiajun Hu; Jixiang Li; Maisideke Maimaitijiang; Yalei Zhang; Shuguang Liu; Rongbing Fu (Chemosphere, 2023)

Eco-friendly approach for enhancing the floatability of non-metallic components in waste printed circuit boards: Adding gutter oil during dry grinding - Chun-chen Nie; Si-qi Jiang; Xi-guang Li; Xiao-ru Wang; Zhi-hao Li; Xiang-nan Zhu; Xian-jun Lyu; Xiao-fang You; Lin Li (Waste Management, 2023)

Energy-efficient fluorine-free electro-refining of crude lead in a green methanesulfonic acid system - You-gang Li; Cong Chang; Jun-jie Qu; Chang-liu Xiang; Tao Luo; Shan-shan Liu; Shuai Li; Sheng-hai Yang; Heng-hui Wang; Xiao-bo Min; Chang-hong Wang; Yong-ming Chen (Journal of Environmental Chemical Engineering, 2023)

Nitrite production mechanism and microbial evolution characteristic influenced by pH during partial denitrification (PD) process - Miao Zhang; Biao Li; Dongbin Wang; Yufei You; Yajun Fan; Jun Wu; Xiaofan Lv (Journal of Environmental Chemical Engineering, 2023)

Widely targeted metabolic profiling provides insights into variations in bioactive compounds and antioxidant activity of sesame, soybean, peanut, and perilla - Habtamu Kefale; Senouwa Segla Koffi Dossou; Feng Li; Nanjun Jiang; Rong Zhou; Lei Wang; Yanxin Zhang; Donghua Li; Jun You; Linhai Wang (Food Research International, 2023)

Metal-organic frameworks (MOFs)-derived Mn2SnO4@C anode based on dual lithium storage mechanism for high-performance lithium-ion capacitors - You-Kang Duan; Zhi-Wei Li; Shi-Chun Zhang; Tong Su; Yan-Fang Ma; Ai-Jun Jiao; Zhen-Hai Fu (Chemical Engineering Journal, 2023)

Factors affecting the accumulation of organotins by wild fish: A case study in the Three Gorges Reservoir, China - Jun-min Gao; Jia You; Jing-cheng Wu; Jin-song Guo; Ping-ting Fu; Li-xia Zhang (Environmental Science and Pollution Research, 2023)

Over-expression of UDP-glycosyltransferase UGT353G2 confers resistance to neonicotinoids in whitefly (Bemisia tabaci) - Tian-hua Du; Cheng Yin; Lian-you Gui; Jin-jin Liang; Shao-nan Liu; Bu-li Fu; Chao He; Jing Yang; Xue-gao Wei; Pei-pan Gong; Ming-jiao Huang; Hu Xue; et al. (Pesticide Biochemistry and Physiology, 2023)

Propeller hydrodynamic excitation influenced by shafting whirling vibration considering different nonuniform inflow conditions: A numerical study - Chang-Lin Meng; Lie-Yi Dong; Dong-Hua Wang; Jia-Xuan He; Zhi-Jun Shuai; Wan-You Li; Shi-Wei Ni; Chen-Xing Jiang (Ocean Engineering, 2023)

Recycling valuable metals from spent lithium-ion battery cathode materials based on microwave-assisted hydrogen reduction followed by grind-leaching and magnetic separation - Jinxiang You; Zhongxiao Qin; Gaohui Wang; Mingjun Rao; Jun Luo; Zhiwei Peng; Shang Zou; Guanghui Li (Journal of Cleaner Production, 2023)

A 3D-Panoramic fusion flood enhanced visualization method for VR - Pei Dang; Jun Zhu; Yuxuan Zhou; Yuting Rao; Jigang You; Jianlin Wu; Mengting Zhang; Weilian Li (Environmental Modelling & Software, 2023)

Stretchable textile with ultra-high electromagnetic interference shielding performance based on porous wrinkled conductive network - Tai-Bao Yang; Ji-You Zong; Hao Lin; Ding-Xiang Yan; Jun Lei; Zhong-Ming Li (Chemical Engineering Journal, 2023)

Reliability analysis of core power optimization control using Kalman filter for accelerator driven system based on reconfigurable computing - Jin-Yang Li; Huan Lin; Long Gu; You-Peng Zhang; Jun-Liang Du; Yong-Quan Wang; Cong Lin; Xing-Chen Zhou; Tian Wang (Annals of Nuclear Energy, 2023)

Resource utilization of rice straw to prepare biochar as peroxymonosulfate activator for naphthalene removal: Performances, mechanisms, environmental impact and applicability in groundwater - Jun Bo Zhang; Chaomeng Dai; Zeyu Wang; Xueji You; Yanping Duan; Xiaoying Lai; Rongbing Fu; Yalei Zhang; Maisideke Maimaitijiang; Kah Hon Leong; Yaojen Tu; Zhi Li (Water Research, 2023)

Effects of interspecific interactions on soil carbon emission and efficiency in the semiarid intercropping systems - Wei Wang; Meng-Ying Li; Rui Zhou; Shuang-Guo Zhu; Hong-Yan Tao; Aziz Khan; Aimee Grace Uzamurera; Bao-Zhong Wang; Jun-Ming Jin; Yue Ma; Wen-Bo Li; Xiu-Ping Tao; et al. (Soil and Tillage Research, 2023)

A review of anaerobic granulation under high-salinity conditions: Mechanisms, influencing factors and enhancement strategies - Chen-Shun Lu; Jin-Ming Qiu; Yang Yang; Yong Hu; Yu-You Li; Takuro Kobayashi; Yong-Jun Zhang (Journal of Water Process Engineering, 2023)

Leaf senescence, nitrogen remobilization, and productivity of maize in two semiarid intercropping systems - Wei Wang; Meng-Ying Li; Rui Zhou; Fei Mo; Aziz Khan; Asfa Batool; Wei Zhang; Jun-Sheng Lu; Ying Zhu; Bao-Zhong Wang; Yu-Miao Yang; Jing Wang; et al. (European Journal of Agronomy, 2023)

A dynamic visualization based on conceptual graphs to capture the knowledge for disaster education on floods - Yukun Guo; Jun Zhu; Jigang You; Saied Pirasteh; Weilian Li; Jianlin Wu; Jianbo Lai; Pei Dang (Natural Hazards, 2023)

LncRNA XIST Exacerbates Oxygen-Glucose Deprivation/Reoxygenation-Induced Cerebral Injury Through the miR-25-3p/TRAF3 Axis - You Li; Ji-Kun Zhang; Zheng-Tao Yu; Jun-Wen Jiang; Hong Tang; Guo-Long Tu; Ying Xia (Molecular Neurobiology, 2023)

Research on stability and control strategies for a spring-loaded valve with bypass outlet - Jie Jian; Zhi-Jun Shuai; Jia-Xuan He; Chang-Lin Meng; Tao Yu; Xi Wang; Wan-You Li; Shi-Wei Ni; Chen-Xing Jiang (Annals of Nuclear Energy, 2023)

Hydrodynamics and sliding posture analysis of the Cambrian arthropod Ercaicunia multinodosa - Yu-Han Li; Zu-Peng Zhou; Da-You Zhai; Robert J. O'Flynn; Jun Tang; Jin-Wei Xu; Xu-Guang Zhou; Yu Liu (Palaeoworld, 2023)

Earthworms synergize with indigenous soil functional microorganisms to accelerate the preferential degradation of the highly toxic S-enantiomer of the fungicide imazalil in soil - Lingxi Han; Kuan Fang; Xiangwei You; Yiqiang Li; Xiuguo Wang; Jun Wang (Journal of Hazardous Materials, 2023)

Novel_miR-1517 mediates CYP6CM1 to regulate imidacloprid resistance in Bemisia tabaci (Hemiptera: Gennadius) - Pei-Pan Gong; Xue-Gao Wei; Shao-Nan Liu; Jing Yang; Bu-Li Fu; Jin-Jin Liang; Ming-Jiao Huang; Tian-Hua Du; Cheng Yin; Yao Ji; Chao He; Jin-Yu Hu; et al. (Pesticide Biochemistry and Physiology, 2023)

Challenges and engineering application of landfill leachate concentrate treatment - Qian Li; Hanlin Cui; Yihao Li; Xin Song; Wenzong Liu; Yongxuan Wang; Haimeng Hou; Hongbo Zhang; You Li; Fan Wang; Jun Song; Hanfeng Ye; et al. (Environmental Research, 2023)

An extremely safe and flexible zinc-ion hybrid supercapacitor based on a scalable, thin and high-performance hierarchical structured gel electrolyte - Shangdong Qin; Chao Wan; Mingwei Xu; Jun Huang; Kui Chen; Qinqin Xu; Shizhao Li; Fazhi Zhang; Yuanlong Guo; Yang You; Haibo Xie (Chemical Engineering Journal, 2023)

Static magnetic field increases aerobic nitrogen removal from hypersaline wastewater in activated sludge with coexistence of fungi and bacteria - Jun Chen; You-Wei Cui; Mei-Qi Huang; Hui-Juan Yan; Dong Li (Bioresource Technology, 2023)

ED-DQN: An event-driven deep reinforcement learning control method for multi-zone residential buildings - Qiming Fu; Zhu Li; Zhengkai Ding; Jianping Chen; Jun Luo; Yunzhe Wang; You Lu (Building and Environment, 2023)

Spatio-and temporal patterns of Jurassic–Early Cretaceous volcanism in the Great Xing’an range, NE China: constraints on the geodynamic evolution - Zong-Yuan Tang; Jie Li; Qing-Yang Li; De-You Sun; Jun Gou; Chang-Zhou Deng (International Geology Review, 2023)

Iodine nanotrap for highly efficient iodine capture under high temperature - Feng Shui; Qiong Lei; Xinglong Dong; Tingting Pan; Zhiyuan Zhang; Jinli Li; Mao Yi; Laiyu Zhang; Xiongli Liu; Zifeng You; Shiqi Yang; Rufeng Yang; et al. (Chemical Engineering Journal, 2023)

Numerical study on unsteady propeller exciting characteristics considering shafting whirling vibration effect - Chang-Lin Meng; Zhi-Jun Shuai; Tao Yu; Ke-Xin Ren; Jie Jian; Xi Wang; Dong-Hua Wang; Wan-You Li; Chen-Xing Jiang (Ocean Engineering, 2023)

Mariculture affects antibiotic resistome and microbiome in the coastal environment - Lu-Xi He; Liang-Ying He; Fang-Zhou Gao; Min Zhang; Jun Chen; Wei-Li Jia; Pu Ye; Yu-Wei Jia; Bai Hong; Si-Si Liu; You-Sheng Liu; Jian-Liang Zhao; et al. (Journal of Hazardous Materials, 2023)

Genome-wide Transcriptome Analysis Reveals the Gene Regulatory Network in Star Fruit Flower Blooming - Si Qin; Xiao-Ping Li; Chun-Mei Wu; Le You; Donghui Peng; Sagheer Ahmad; Hui Ren; Zhong-Jian Liu; Jun-Wen Zhai; Sha-Sha Wu (Tropical Plant Biology, 2023)

The presence of soybean, but not soybean cropping frequency has influence on SOM priming in crop rotation systems - Shan-Shan Dai; Peng He; Meng-Yang You; Lu-Jun Li (Plant and Soil, 2023)

CircFhit Modulates GABAergic Synaptic Transmission via Regulating the Parental Gene Fhit Expression in the Spinal Dorsal Horn in a Rat Model of Neuropathic Pain - Ting Xu; Zhen-Yu Li; Meng Liu; Su-Bo Zhang; Huan-Huan Ding; Jia-Yan Wu; Su-Yan Lin; Jun Liu; Jia-You Wei; Xue-Qin Zhang; Wen-Jun Xin (Neuroscience Bulletin, 2023)

Straw return, rather than warming, alleviates microbial phosphorus limitation in a cultivated Mollisol - Xuechen Yang; Peng He; Zhiming Zhang; Mengyang You; Xuefeng Wu; Lu-Jun Li (Applied Soil Ecology, 2023)

Isolation and stereospecific synthesis of indole alkaloids with lipid-lowering effects from the marine-derived fungus Colletotrichum gloeosporioides BB4 - Qin Huang; Meng-Jiao Hao; Lai-You Wang; Feng Wu; Hou-Jin Li; Jie Yuan; Jun Xu; Taifo Mahmud; Wen-Jian Lan (Phytochemistry, 2023)

Intercropped soybean boosts nitrogen benefits and amends nitrogen use pattern under plastic film mulching in the semiarid maize field - Wei Zhang; Yong-Xian Wei; Aziz Khan; Jun-Sheng Lu; Jun-Lan Xiong; Shuang-Guo Zhu; Xiang-Wen Fang; Wei Wang; Meng Hao; Ling Zhao; Xiao-Lin Zhang; Jian-Ming Deng; et al. (Field Crops Research, 2023)

Intelligent shielding material based on VO2 with tunable near-field and far-field electromagnetic response - Si-Yuan Liao; Xiao-Yun Wang; Hai-Peng Huang; Yu-Ying Shi; Qiao-Feng Wang; You-Gen Hu; Peng-Li Zhu; Rong Sun; Ching-Ping Wong; Yan-Jun Wan (Chemical Engineering Journal, 2023)

Dosage effect of anthocyanin biosynthesis in purple-grained wheat (Triticum aestivum L.) - Chan Bi; Chaoxiong Wei; Shuai Tian; Jinghui Li; Yufeng Zhang; Jun Ma; Mingshan You (Euphytica, 2023)

Karst-ecological changes during the middle and late Holocene in Southwest China revealed by δ18O and δ13C records in a stalagmite - Rong Duan; Ting-Yong Li; Jun-Yun Li; Christoph Spötl; Hong-Chun Li; Hai-Bo Wang; Hai Cheng; You-Feng Ning; Chuan-Chou Shen; Jing-Li Zhou; Chao-Jun Chen; Tsai-Luen Yu; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Selenite reduced uptake/translocation of cadmium via regulation of assembles and interactions of pectins, hemicelluloses, lignins, callose and Casparian strips in rice roots - LiZhen Wang; KongYuan Wu; ZiQing Liu; ZengFei Li; Jun Shen; ZiHan Wu; Hong Liu; LeXing You; GuiDi Yang; Christopher Rensing; RenWei Feng (Journal of Hazardous Materials, 2023)

ARHGEF15 is expressed in undifferentiated spermatogonia but is not required for spermatogenesis in mice - Yu-Jun Wang; Shuang Li; Hai-Ping Tao; Xiao-Na Zhang; You-Gui Fang; Qi-En Yang (Reproductive Biology, 2023)

Single aromatics sulfonamide substituted dibenzothiazole squaraines for tumor NIR imaging and efficient photodynamic therapy at low drug dose - Jun-Hui Li; Pei-Dan You; Fei Lu; Jun-Tao Huang; Jia-Luo Fu; Hao-Yun Tang; Chun-Qiong Zhou (Journal of Photochemistry and Photobiology B: Biology, 2023)

DEGENERATED LEMMA (DEL) regulates lemma development and affects rice grain yield - You Jing; Chen Wenbo; He Zhifeng; Xiang Yan; Zhang XinFang; Wei Mi; Wu RuHui; Shen Wenqiang; Zhang Jun; Duan QianNan; He Guanghua; Li Yunfeng; et al. (Physiology and Molecular Biology of Plants, 2023)

A Method for Accurate Measuring the Tensile Strength of Single Rock Grain Interface - Zhi-Jun Wu; Zhi-Yang Wang; You Wu; Xue-Yao Wang; Quan-Sheng Liu; Ying-Wei Li (Rock Mechanics and Rock Engineering, 2023)

Evaluation of deep learning algorithms for landslide susceptibility mapping in an alpine-gorge area: a case study in Jiuzhaigou County - Di Wang; Rong-hao Yang; Xiao Wang; Shao-da Li; Jun-xiang Tan; Shi-qi Zhang; Shuo-you Wei; Zhang-ye Wu; Chao Chen; Xiao-xia Yang (Journal of Mountain Science, 2023)

Large-scale mariculture of the sponge Haliclona simulans on floating rafts in Zhao'an Bay, Fujian Province, China - Zhunfei Li; Guangyuan Xia; Huilong Ou; Ming Chen; Yingzhe You; Jun Chen (Aquaculture, 2023)

Variations in Asian summer monsoon and hydroclimate during Heinrich stadials 4 revealed by stalagmite stable isotopes and trace elements - Yao Wu; Ting-Yong Li; Jun-Yun Li; Hai Cheng; You-Feng Ning; Chuan-Chou Shen; Yan Yang; Jing-Yao Zhao; Chao-Jun Chen; Ming-Qiang Liang; Si-Ya Xiao; Hai-Ying Qiu; et al. (Quaternary Science Reviews, 2023)

Thermodynamic characteristics of methane hydrate formation in high-pressure microcalorimeter under different reaction kinetics - Juan Fu; Jia-Mei Mo; Shi-Jun Liu; Wen-Zhe Yi; Yi-Song Yu; Neng-You Wu; Xiao-Li Chen; Qiu-Cheng Su; Xiao-Sen Li (Fuel, 2023)

Liquid metal embrittlement to boost reactivity and combustion performance of Al in composite propellants - An Chen; Bo Wu; Lan Li; Ting You; Jun Wang; Jinpeng Shen; Chonghua Pei (Fuel, 2023)

A self-priming air filtration system based on triboelectric nanogenerator for active air purification - Chang-Long Li; Wei-Zhi Song; De-Jun Sun; Meng Zhang; Jun Zhang; You-Qiang Chen; Seeram Ramakrishna; Yun-Ze Long (Chemical Engineering Journal, 2023)

Salt Bridge-intermediated three phase decoupling electrolytes for high voltage electrolytic aqueous Zinc-Manganese dioxides battery - Qi Xu; Qi-Xing Xie; Tong Xue; Gao Cheng; Jian-Dong Wu; Lan Ning; Xiang-Hui Yan; You-Jun Lu; Zhong-Li Zou; Bei-Ping Wang; Feng-Lan Han (Chemical Engineering Journal, 2023)

Correction to: Niche differentiation and higher uptake of available nitrogen maintained the productivity of alpine meadow at early degradation - Chimin Lai; Fei Peng; Jianbo Sun; Jun Zhou; Chengyang Li; Xingliang Xu; Xiaojie Chen; Quangang You; Hongyang Sun; Jian Sun; Xian Xue; Hans Lambers (Biology and Fertility of Soils, 2023)

Niche differentiation and higher uptake of available nitrogen maintained the productivity of alpine meadow at early degradation - Chimin Lai; Fei Peng; Jianbo Sun; Jun Zhou; Chengyang Li; Xingliang Xu; Xiaojie Chen; Quangang You; Hongyang Sun; Jian Sun; Xian Xue; Hans Lambers (Biology and Fertility of Soils, 2023)

Relation of Carotid Plaque Features Detected with Ultrasonography-Based Radiomics to Clinical Symptoms - Zhe Huang; Xue-Qing Cheng; Hong-Yun Liu; Xiao-Jun Bi; Ya-Ni Liu; Wen-Zhi Lv; Li Xiong; You-Bin Deng (Translational Stroke Research, 2022)

Recent development in zebrafish model for bioactivity and safety evaluation of natural products - Fang-Jun Lin; Hang Li; Ding-Tao Wu; Qi-Guo Zhuang; Hua-Bin Li; Fang Geng; Ren-You Gan (Critical Reviews in Food Science and Nutrition, 2022)

Sexual size dimorphism in golden pompano (Trachinotus blochii): Potential roles of changes in energy allocation and differences in muscle metabolism - Jun Long Sun; Fei Biao Song; Lei Wang; Wei Wei Zhang; You Ming Chen; Li Zhou; Jian Fang Gui; Jian Luo (Frontiers in Marine Science, 2022)
Golden pompano ( Trachinotus blochii ) is becoming increasingly popular and produces high yields, but the growth differences between males and females are a concern. In this study, the differences between the growth of males and females were compared, and the transcriptome analysis of muscle tissues was performed. A significant difference between the growth of males and females was observed; females were found to be 17% larger than males after reaching 7 months of age. Gonadal histological analysis revealed that the ovaries were arrested in 7- to 9-month-old golden pompano, whereas the testes continued to develop. The AMPK and adipocytokine signaling pathways were also found to be involved in the regulation of muscle growth and metabolism. After reaching 7 months of age, the expression levels of glut1 , glut4 , ldh , gys, acsl and cpt2 in the muscle of females were lower than those in males, but the hk gene, which is involved in glycolysis, was found to remain highly expressed in females. Additionally, in females, the synthesis of arginine and ornithine and the production of carnosine were found to be inhibited, but the breakdown of glutamine was found to be enhanced and OXPHOS ability was found to be stronger in females after reaching 7 months of age. These results support a certain negative correlation between gonadal development and muscle metabolism depending on differences in energy distribution. Clearly, the faster growth in females after reaching 7 months of age was found to be associated with the more active metabolism of glucose, and amino acids, as well as stronger oxidative phosphorylation levels.

Effect modification by aging on the associations of nicotine exposure with cognitive impairment among Chinese elderly - Jian Hou; Chao Huang; Bo Zhu; Wei Liu; Qing-qing Zhu; Lu Wang; Tian Li; Chun-jie Yuan; Shao-yang Lai; De-sheng Wu; Fei-qi Zhu; Jia-fei Zhang; et al. (Environmental Science and Pollution Research, 2022)

Aculeaquamide A, cytotoxic paraherquamide from the marine fungus Aspergillus aculeatinus WHUF0198 - Jun Wu; Fuqian Wang; Li-Ming He; Si-Yuan Zhou; Shou-Bao Wang; Jia Jia; Kui Hong; You-Sheng Cai (Natural Product Research, 2022)

PLXDC2 enhances invadopodium formation to promote invasion and metastasis of gastric cancer cells via interacting with PTP1B - Bin Wu; Yan-xia Wang; Jun-jie Wang; Dong-fang Xiang; Meng-si Zhang; Ze-xuan Yan; Wen-ying Wang; Jing-ya Miao; Xi Lan; Jia-jia Liu; Zheng-yan Li; Chuan Li; et al. (Clinical & Experimental Metastasis, 2022)
Plexin-domain containing 2 (PLXDC2) has been reported as an oncoprotein in several human malignancies. However, its expression and roles in gastric cancer remain largely unclear. In this study, we found that PLXDC2 was highly expressed in gastric cancer tissues, and the expression levels were positively correlated with clinicopathological features, but negatively with the patients’ outcome. Cox regression analysis identified PLXDC2 as an independent prognostic indicator for the patients. Knockdown of PLXDC2 markedly suppressed the in vitro invasion and in vivo metastasis of gastric cancer cells, while overexpression of PLXDC2 resulted in opposite effects. Mechanistically, PLXDC2 enhanced the level of phosphorylated Cortactin (p-Cortactin) by physically interacting with protein tyrosine phosphatase 1B (PTP1B), an important dephosphorylase, to prevent its dephosphorylating of p-Cortactin, thereby promoting the formation of invadopodia. Collectively, our results indicate that PLXDC2 contributes to the invasion and metastasis of gastric cancer by inhibiting PTP1B to facilitate the invadopodium formation, and may serve as a potential prognostic biomarker and a therapeutic target for this disease.

Pharmacokinetics of benapenem for injection in subjects with mild to moderate renal impairment - Haijing Yang; Min Zhang; Yuancheng Chen; Hong Ren; Hong Zhang; Chen Yu; Jianda Lu; Li You; Jicheng Yu; Hong Liang; Cuilan Xiao; Zishuang He; et al. (European Journal of Clinical Pharmacology, 2022)

Erratum to: Estimating the maximum impact force of dry granular flow based on pileup characteristics - Si-you Xiao; Li-jun Su; Yuan-jun Jiang; Alam Mehtab; Cheng Li; Dao-chuan Liu (Journal of Mountain Science, 2022)

Alternate freezing and thawing enhanced the sediment and nutrient runoff loss in the restored soil of the alpine mining area - Fa-Yong Li; Ren-jie Luo; Yong-jun You; Xue-fei Hu; Xiao-yan Qian; Peng-yan Zhang; Shan Wang; Guo-yu Li; Mohamed Eltohamy Kamel (Journal of Mountain Science, 2022)

Kai-Xin-San Inhibits Tau Pathology and Neuronal Apoptosis in Aged SAMP8 Mice - Ya-Nan Jiao; Jing-Sheng Zhang; Wen-Jun Qiao; Shu-Yu Tian; Yi-Bin Wang; Chun-Yan Wang; Yan-Hui Zhang; Qi Zhang; Wen Li; Dong-Yu Min; Zhan-You Wang (Molecular Neurobiology, 2022)
Alzheimer’s disease (AD) is an age-related neurological disorder. Currently, there is no effective cure for AD due to its complexity in pathogenesis. In light of the complex pathogenesis of AD, the traditional Chinese medicine (TCM) formula Kai-Xin-San (KXS), which was used for amnesia treatment, has been proved to improve cognitive function in AD animal models. However, the active ingredients and the mechanism of KXS have not yet been clearly elucidated. In this study, network pharmacology analysis predicts that KXS yields 168 candidate compounds acting on 863 potential targets, 30 of which are associated with AD. Enrichment analysis revealed that the therapeutic mechanisms of KXS for AD are associated with the inhibition of Tau protein hyperphosphorylation, inflammation, and apoptosis. Therefore, we chose 7-month-old senescence-accelerated mouse prone 8 (SAMP8) mice as AD mouse model, which harbors the behavioral and pathological hallmarks of AD. Subsequently, the potential underlying action mechanisms of KXS on AD predicted by the network pharmacology analyses were experimentally validated in SAMP8 mice after intragastric administration of KXS for 3 months. We observed that KXS upregulated AKT phosphorylation, suppressed GSK3β and CDK5 activation, and inhibited the TLR4/MyD88/NF-κB signaling pathway to attenuate Tau hyperphosphorylation and neuroinflammation, thus suppressing neuronal apoptosis and improving the cognitive impairment of aged SAMP8 mice. Taken together, our findings reveal a multi-component and multi-target therapeutic mechanism of KXS for attenuating the progression of AD, contributing to the future development of TCM modernization, including KXS, and broader clinical application. Graphical abstract

Proteomic characterization of four subtypes of M2 macrophages derived from human THP-1 cells - Pengfei Li; Chen Ma; Jing Li; Shanshan You; Liuyi Dang; Jingyu Wu; Zhifang Hao; Jun Li; Yuan Zhi; Lin Chen; Shisheng Sun (Journal of Zhejiang University-SCIENCE B, 2022)

RhoGDI2 induced malignant phenotypes of pancreatic cancer cells via regulating Snail expression - Bin Yi; You Hu; Dongming Zhu; Jun Yao; Jian Zhou; Yi Zhang; Zhilong He; Lifeng Zhang; Zixiang Zhang; Jian Yang; Yuchen Tang; Yujie Huang; et al. (Genes & Genomics, 2022)

Crocin Alleviates Intracerebral Hemorrhage–Induced Neuronal Ferroptosis by Facilitating Nrf2 Nuclear Translocation - Fei Wang; Wu-lin Li; Li-juan Shen; Ting-ting Jiang; Jian-jun Xia; Da-li You; Shan-you Hu; Li Wang; Xiao Wu (Neurotoxicity Research, 2022)

Petrogenesis and tectonic setting of the early-middle triassic subduction-related granite in the eastern segment of East Kunlun: evidences from petrology, geochemistry, and zircon U-Pb-Hf isotopes - Zuo-Chen Li; Xian-Zhi Pei; Paul D. Bons; Rui-Bao Li; Lei Pei; Guo-Chao Chen; You-Xin Chen; Cheng-Jun Liu; Meng Wang; Shao-Wei Zhao; Xiao-Bing Li; Feng Gao (International Geology Review, 2022)

Transcriptomic analyses reveal the effect of nitric oxide on the lateral root development and growth of mangrove plant Kandelia obovata - Ming-Yue Wei; Huan Li; You-Hui Zhong; Zhi-Jun Shen; Dong-Na Ma; Chang-Hao Gao; Yi-Ling Liu; Wen-Hua Wang; Jing-Ya Zhang; Yan-Ping You; Hai-Lei Zheng (Plant and Soil, 2022)

Haloterrigena gelatinilytica sp. nov., a new extremely halophilic archaeon isolated from salt-lake - Bing-Bing Liu; Nimaichand Salam; Manik Prabhu Narsing Rao; Shuang Cheng; Yuan-Guo Xie; Lai-You Wang; Yuan-ru Zhang; Xin-Yuan Yu; Shu-xian Guo; Wen-Jun Li (Archives of Microbiology, 2022)

Genetic improvement of grain quality traits in indica inbred rice cultivars developed in South China during 1956–2020 - Xin-Qiao Zhou; Da-Gang Chen; Jie Guo; Ping-Li Chen; Li-Jun Li; Ke Chen; You-Ding Chen; Chuan-Guang Liu; Ze-Min Zhang (Euphytica, 2022)

Assessment of probiotic adhesion and inhibitory effect on Escherichia coli and Salmonella adhesion - Ya Wang; Dan Jia; Jia-hui Wang; He-hai Li; Jun-long Liu; Ai-hong Liu; Jin-ming Wang; Gui-quan Guan; Jian-xun Luo; Hong Yin; You-quan Li (Archives of Microbiology, 2021)

Mobilization of soil phosphate after 8 years of warming is linked to plant phosphorus‐acquisition strategies in an alpine meadow on the Qinghai‐Tibetan Plateau - Jun Zhou; Xiao‐Long Li; Fei Peng; Chengyang Li; Chimin Lai; Quangang You; Xian Xue; Yanhong Wu; Hongyang Sun; Yang Chen; Hongtao Zhong; Hans Lambers (Global Change Biology, 2021)
Phosphorus (P) is essential for productivity of alpine grassland ecosystems, which are sensitive to global warming. We tested the hypotheses that (1) mobilized ‘calcium‐bound inorganic P’ (Ca‐P i ) is a major source of plant‐available P in alpine meadows with alkaline soils after long‐term warming, (2) mobilization of Ca‐P i is linked to effective plant carboxylate‐releasing P‐acquisition strategies under warming, and (3) the mobilization is also related to plant nitrogen (N)‐acquisition. We conducted an 8‐year warming experiment in an alpine meadow (4635 m above sea level) on the Qinghai‐Tibetan Plateau. A significant increase in P concentration in both aboveground and belowground biomass indicates an increased mobilization and assimilation of P by plants under warming. We observed a significant decrease in Ca‐P i , no change in moderately‐labile organic P, and an increase in highly resistant organic P after warming. There was no increase in phosphatase activities. Our results indicate that Ca‐P i , rather than organic P was the major source of plant‐available P for alpine meadows under warming. Higher leaf manganese concentrations of sedges and forbs after warming indicate that carboxylates released by these plants are a key mechanism of Ca‐P i mobilization. The insignificant increase in Rhizobiales after warming and the very small cover of legumes show a minor role of N‐acquisition strategies in solubilizing phosphate. The insignificant change in relative abundance of mycorrhizal fungi and bacteria related to P cycling after warming shows a small contribution of microorganisms to Ca‐P i mobilization. The significant increase in leaf N and P concentrations and N:P ratio of grasses and no change in sedge leaf N:P ratio reflect distinct responses of plant nutrient status to warming due to differences in P‐acquisition strategies. We highlight the important effects of belowground P‐acquisition strategies, especially plant carboxylate‐releasing P‐acquisition strategies on responses of plants to global changes in alpine meadows.

Induced production of a new polyketide in Penicillium sp. HS-11 by chemical epigenetic manipulation - You-Min Ying; Ling Li; Hang-Fei Yu; Yi-Lian Xu; Lu Huang; Wei Mao; Cui-Ping Tong; Zhi-Dong Zhang; Zha-Jun Zhan; Yun Zhang (Natural Product Research, 2021)

CCN1 gene polymorphisms associated with congenital heart disease susceptibility in Northwest Chinese population from different high-altitude areas - Wenke Yang; Jun Bai; Xinyu Song; Shasha Zhang; Nana Chen; Tao You; Kang Yi; Zhenglin Li; Dingxiong Xie; Xiaodong Xie (Environmental Science and Pollution Research, 2021)

MiR-137 inhibits the proliferation, invasion and migration of glioma via targeting to regulate EZH2 - Jingshun Gu; Juntong Wang; Aiwu You; Jun Li; Yuyan Zhang; Guomin Rao; Xuehua Ge; Kun Zhang; Xuan Liu; Dongchun Wang (Genes & Genomics, 2021)

Fast estimation method of volumes of landslide deposit by the 3D reconstruction of smartphone images - Lin Fu; Jun Zhu; Wei-lian Li; Ji-gang You; Zhang-yu Hua (Landslides, 2021)

Application of Plant Print Identification Technology in Salt-resistant Soybean Breeding - Yan Li; Xia Li; Zi-qi Chen; Ying Ma; Guang-yu Yang; Ying Zhang; Ming-chun Sun; Li-hong Zhang; Jin-meng Chu; Jing-mei Lu; Jun Zhu; Ji-hong You (Journal of Plant Growth Regulation, 2021)

Ghrelin Affects Gastric Cancer Progression by Activating AMPK Signaling Pathway - Xiao-Lin Hu; Yong-Jun Zhu; Chang-Hua Hu; Li You; Juan Wu; Xiao-Yan He; Wen-Jie Huang; Zong-Hui Wu (Biochemical Genetics, 2021)

Experimental validation of a new semi-empirical impact force model of the dry granular flow impact against a rigid barrier - Yuan-Jun Jiang; Xiao-Yi Fan; Li-Jun Su; Si-you Xiao; Jing Sui; Rui-Xiao Zhang; Yue Song; Zhi-Wen Shen (Landslides, 2021)

Vulnerability assessment of crop production to climate change across Northwest China during 1995–2014 - You-jia Liang; Li-jun Liu (Journal of Mountain Science, 2021)

Empirical relations for conversion of surface- and body-wave magnitudes to moment magnitudes in China’s seas and adjacent areas - Zhuo-Juan Xie; Shan-You Li; Yue-Jun Lyu; Wei-Jin Xu; Yu-ling Zhang (Journal of Seismology, 2021)

Cerebral microbleeds and their influence on cognitive impairment in Dialysis patients - Yujun Qian; Ke Zheng; Haiyun Wang; Hui You; Fei Han; Jun Ni; Bo Hou; Limeng Chen; Yicheng Zhu; Feng Feng; Xuemei Li (Brain Imaging and Behavior, 2021)

Antibody response and therapy in COVID-19 patients: what can be learned for vaccine development? - Ligong Lu; Hui Zhang; Meixiao Zhan; Jun Jiang; Hua Yin; Danielle J. Dauphars; Shi-You Li; Yong Li; You-Wen He (Science China Life Sciences, 2020)

Dietary lipid concentrations influence growth, body composition, morphology of the liver and mid-intestine, and antioxidant status of marbled eel (Anguilla marmorata) - Shi-Jun Chen; Peng Liu; You-Ming Jia; Hong-Ping Liao; Shao-Xuan Zhu; Li-Liu Zhou; Xue-Ming Dan; Li Liu; Jia-Hao Li; Su-Bi Zheng; Jun-Jiang Yang; Lian Gan (Aquaculture International, 2020)

Solanrubiellin A, a hydroanthraquinone dimer with antibacterial and cytotoxic activity from Solanum lyratum - Hui Chen; Kun Du; Yan-Jun Sun; Zhi-You Hao; Yan-Li Zhang; Jiang Bai; Qing-Hua Wang; Hai-Yu Hu; Wei-Sheng Feng (Natural Product Research, 2020)

Enhanced tenogenic differentiation and tendon-like tissue formation by Scleraxis overexpression in human amniotic mesenchymal stem cells - Xizhong Zhu; Ziming Liu; Shuhong Wu; Yuwan Li; Huazhang Xiong; Gang Zou; Ying Jin; Jibin Yang; Qi You; Jun Zhang; Yi Liu (Journal of Molecular Histology, 2020)

Targeting gut microbiota with dietary components on cancer: Effects and potential mechanisms of action - Jun Tao; Sha Li; Ren-You Gan; Cai-Ning Zhao; Xiao Meng; Hua-Bin Li (Critical Reviews in Food Science and Nutrition, 2020)

Rapid detection of Anguina agrostis by loop-mediated isothermal amplification - Lu-zhen Yu; Shao-yi Song; Cui Yu; Bin-bin Jiao; Yi-min Tian; You-jun Li (European Journal of Plant Pathology, 2020)

Bioavailable phosphorus distribution in alpine meadow soil is affected by topography in the Tian Shan Mountains - Fa-Yong Li; Cheng-yu Yuan; Zi-Qiang Yuan; Yong-jun You; Xue-fei Hu; Shan Wang; Guo-yu Li (Journal of Mountain Science, 2020)

The false smut pathogen Ustilaginoidea virens requires rice stamens for false smut ball formation - Jing Fan; Jie Liu; Zhi‐You Gong; Pei‐Zhou Xu; Xiao‐Hong Hu; Jin‐Long Wu; Guo‐Bang Li; Juan Yang; Yu‐Qiu Wang; Yu‐Feng Zhou; Shuang‐Cheng Li; Li Wang; et al. (Environmental Microbiology, 2020)
Summary Rice false smut has emerged as a serious grain disease in rice production worldwide. The disease is characterized by the transformation of individual rice florets into false smut balls, which is caused by the fungal pathogen Ustilaginoidea virens . To date, little is known about the host factors required for false smut ball formation by U . virens . In this study, we identified histological determinants for the formation of false smut balls by inoculating U . virens into rice floral mutants defective with respect to individual floral parts. The results showed that U . virens could form mature false smut balls in rice floral mutants with defective pistils, but failed to develop false smut balls in the superwoman mutant lacking stamens, identifying that U . virens requires rice stamens to complete its infection cycle. Comparative transcriptome analysis indicated a list of candidate host genes that may facilitate nutrient acquisition by U . virens from the rice stamens, such as SWEET11 , SWEET14 and SUT5 , and genes involved in the biosynthesis of trehalose and raffinose family sugars. These data pinpoint rice stamens as the key target organ of U . virens infection and provide a valuable starting point for dissecting the molecular mechanism of false smut ball formation.

Reef-carbonate diagenesis in the Pleistocene–Holocene of the well Xike#1, Xisha Islands, South China Sea: implications on sea-level changes - Na Liu; Zhen-feng Wang; Xu-shen Li; Li Liu; Dao-jun Zhang; Li You; Wei Luo; Xin-yu Liu (Carbonates and Evaporites, 2019)

Interception of sulfate deposition from a closed canopy to a forest gap edge canopy in a subalpine dragon spruce plantation - Yu Zhang; Fu-zhong Wu; Bo Tan; Zhen-feng Xu; Han Li; Jun-cheng Liu; Hai-rong Zhao; Si-yi Tan; Cheng-ming You; Wan-qin Yang (Journal of Mountain Science, 2019)

Root diversity in sesame (Sesamum indicum L.): insights into the morphological, anatomical and gene expression profiles - Ruqi Su; Rong Zhou; Marie Ali Mmadi; Donghua Li; Lu Qin; Aili Liu; Jianqiang Wang; Yuan Gao; Mengyuan Wei; Lisong Shi; Ziming Wu; Jun You; et al. (Planta, 2019)

QTL mapping and genetic effect of chromosome segment substitution lines with excellent fiber quality from Gossypium hirsutum × Gossypium barbadense - Shao-qi Li; Ai-ying Liu; Ling-lei Kong; Ju-wu Gong; Jun-wen Li; Wan-kui Gong; Quan-wei Lu; Peng-tao Li; Qun Ge; Hai-hong Shang; Xiang-hui Xiao; Rui-xian Liu; et al. (Molecular Genetics and Genomics, 2019)

The faster-onset antidepressant effects of hypidone hydrochloride (YL-0919) - Li-jun Sun; Li-ming Zhang; Dan Liu; Rui Xue; Yan-qin Liu; Lei Li; Ying Guo; Chao Shang; Jun-qi Yao; You-zhi Zhang; Yun-feng Li (Metabolic Brain Disease, 2019)

Estimating the maximum impact force of dry granular flow based on pileup characteristics - Si-you Xiao; Li-jun Su; Yuan-jun Jiang; Alam Mehtab; Cheng Li; Dao-chuan Liu (Journal of Mountain Science, 2019)

MicroRNAs Involved in the Regulation of LC-PUFA Biosynthesis in Teleosts: miR-33 Enhances LC-PUFA Biosynthesis in Siganus canaliculatus by Targeting insig1 which in Turn Upregulates srebp1 - Jun Jun Sun; Li Guo Zheng; Cui Ying Chen; Jin Ying Zhang; Cui Hong You; Qing Hao Zhang; Hong Yu Ma; Óscar Monroig; Douglas R. Tocher; Shu Qi Wang; Yuan You Li (Marine Biotechnology, 2019)

Study of the Relationship Between the Oil Content of Oil Sands and Spectral Reflectance Based on Spectral Derivatives - Ruixue Fan; Lixin Xing; Jun Pan; Xuanlong Shan; Jinfeng You; Changwei Li; Weijing Zhong (Journal of the Indian Society of Remote Sensing, 2019)

Network of microRNA-transcriptional factor-mRNA in cold response of turbot Scophthalmus maximus - Miaomiao Nie; Xungang Tan; Yunliang Lu; Zhihao Wu; Jun Li; Dongdong Xu; Peijun Zhang; Feng You (Fish Physiology and Biochemistry, 2019)

Numerical analysis of hard rock blasting unloading effects in high in situ stress fields - Si-You Xiao; Li-Jun Su; Yuan-Jun Jiang; Zhi-Xiang Liu (Bulletin of Engineering Geology and the Environment, 2019)

OsDCL3b affects grain yield and quality in rice - Peng-Fei Liao; Jie-Xiu Ouyang; Jian-Jun Zhang; Lan Yang; Xin Wang; Xiao-Jue Peng; Dong Wang; You-Lin Zhu; Shao-Bo Li (Plant Molecular Biology, 2019)

Application of a proton quantitative nuclear magnetic resonance spectroscopy method for the determination of actinodaphnine in Illigera aromatica and Illigera henryi - Jian-Wei Dong; Xue-Jiao Li; Jun-You Shi; Kai-Quan Liu (Journal of Natural Medicines, 2019)

Virulence regulation of cel‐ EIIB protein mediated PTS system in Streptococcus agalactiae in Nile tilapia - Jun Xu; Yun‐Dan Xie; Ling Liu; Song Guo; You‐Lu Su; An‐Xing Li (Journal of Fish Diseases, 2019)
Streptococcus agalactiae is a major pathogen of tilapia causing significant economic losses for the global aquatic industry yearly. To elucidate the role of cel‐ EIIB protein‐mediated phosphotransferase systems ( PTS ) in the virulence regulation of S. agalactiae , cel‐ EIIB gene deletion in a virulent strain THN 0901 was achieved by homologous recombination. The cellobiose utilization of △ cel‐ EIIB strain was significantly decreased relative to S.a . THN 0901 strain incubating in LB with 10 mg/ ml cellobiose ( p cel‐ EIIB strain was also significantly decreased when cultured in BHI medium ( p cel‐ EIIB strain was dramatically decreased (20%), of which S.a . THN 0901 strain and △ cel‐ EIIB ::i strain were 53.33% and 50%, respectively. The competition experience using tilapia model indicated the invasion and colonization ability of △ cel‐ EIIB strain was significantly weaker than that of S.a . THN 0901 strain ( p cel‐ EIIB ::i strain, the mRNA expression of csrS , csrR , rgfA, rgfC, bgrR and bgrS was significantly downregulated in △ cel‐ EIIB strain ( p EIIB protein‐mediated cel‐ PTS not only contributes to biofilm formation and virulence regulation, but also plays an important role in the invasion and colonization of S. agalactiae .

Offspring sex ratio and reproductive tactics of Leptocybe invasa (Hymenoptera: Eulophidae): testing the effect of environmental characteristics - Xia-Lin Zheng; Kai Lin; Zong-You Huang; Jun Li; Zhen-De Yang; Xiu-Hao Yang; Wen Lu (International Journal of Tropical Insect Science, 2018)

Presence of rat bocavirus in oropharyngeal and fecal samples from murine rodents in China - Yi-Quan Xiong; Jun-Hua Zhou; Min-Yi Zhang; Fang-Fei You; Dong-Liang Li; Qing Chen (Archives of Virology, 2018)

Neutrophil-to-Lymphocyte Ratio Is an Independent Predictor of 30-Day Mortality of Intracerebral Hemorrhage Patients: a Validation Cohort Study - Fei Wang; Li Wang; Ting-ting Jiang; Jian-jun Xia; Feng Xu; Li-juan Shen; Wen-hui Kang; Yong Ding; Li-xia Mei; Xue-feng Ju; Shan-you Hu; Xiao Wu (Neurotoxicity Research, 2018)

Parasitoids of the eucalyptus gall wasp Leptocybe spp.: a global review - Zong-You Huang; Jun Li; Wen Lu; Xia-Lin Zheng; Zhen-De Yang (Environmental Science and Pollution Research, 2018)

Investigation of the rheological behavior of activated sludge in response to CeO2 nanoparticles and potential mechanism - Guoxiang You; Peifang Wang; Jun Hou; Chao Wang; Jin Qian; Yanhui Ao; Juan Chen; Lingzhan Miao; Yi Xu; Tao Feng; Li Tao (Environmental Science and Pollution Research, 2018)

Identification and Field Evaluation of the Sex Pheromone of Orthaga achatina (Lepidoptera: Pyralidae) - Qi Yan; Hai-Dong Li; Yan Chen; Zhan-Feng Ye; Xi-Yu You; Jun Zhou; Lan-Fang Mu; Shi-Jing Liu; Xiang-Bo Kong; Sajjad Ali Khuhro; Shuang-Lin Dong (Journal of Chemical Ecology, 2018)

Comparative performance of growth, vertebral structure and muscle composition in diploid and triploid Paralichthys olivaceus - Hui Liu; Zhihao Wu; Xiangping Zhu; Zongcheng Song; Jinwei Hu; Lijuan Wang; Jun Li; Feng You (Journal of Fish Diseases, 2018)
Growth, skeletal structure and muscle composition of cold‐shock‐induced triploid olive flounder Paralichthys olivaceus were investigated. The average values of total length and total weight of triploids were higher than those of diploids from 5 to 11 months posthatch (mph). The growth difference disappeared after 11 mph. The skeletal structure of flounder at 11 mph was observed by X‐ray imaging method. There are four kinds of vertebral deformity including vertebrae fusion, one‐sided compression, two‐sided compression and vertically shifted. The trunk region (V8–18) and tailing end of the vertebral column were the predominant locations of deformity. In general, the frequencies of vertebral deformities in triploids (60.0%) were higher than those in diploids (33.3%, p 0.05). Both the number of fish with deformed vertebrae and the average frequencies of deformed vertebrae in triploids were significantly higher than those in diploids ( p 0.05). The muscle tissues of diploid and triploid flounder at 11 mph contain the same types of fatty acid and free amino acid profiles. The number of fatty acids with significant higher contents in diploids and triploids was one and ten, respectively ( p 0.05). The contents of free amino acids showed no difference between triploid and diploid fish.

Identification of Neoscytalidium dimidiatum causing canker disease of pitaya in Hainan, China - Min Xu; Yun Peng; Zhao Qi; Zhen Yan; Lu Yang; Meng-Die He; Qing-Xiu Li; Cheng-Li Liu; Yun-Ze Ruan; Shuang-Shuang Wei; Jun Xie; You-Quan Xia; et al. (Australasian Plant Pathology, 2018)

Enhanced catalytic activities and modified substrate preferences for taxoid 10β-O-acetyl transferase mutants by engineering catalytic histidine residues - Lin-Feng You; Jia-Jun Huang; Tao Wei; Shu-Ling Lin; Bing-Hua Jiang; Li-Qiong Guo; Jun-Fang Lin (Biotechnology Letters, 2018)

Description of a new species of Triplophysa (Teleostei: Nemacheilidae) from Guizhou Province, China - Wei‐Jun Wu; An‐You He; Jun‐Xing Yang; Li‐Na Du (Journal of Fish Biology, 2018)
A new cave‐dwelling fish species Triplophysa guizhouensis is described based on specimens collected from Guizhou, China, in a subterranean system interconnected with the Hongshui River drainage. The species can be distinguished from its congeners by a combination of characters: eyes present; caudal fin with 14 branched rays; inner gill rakers of first gill arch 8–10; posterior chamber of air bladder developed; and body posterior of dorsal fin scaled. A key to species of Triplophysa in the Pearl River basin is provided.

Social Isolation During Adolescence Induces Anxiety Behaviors and Enhances Firing Activity in BLA Pyramidal Neurons via mGluR5 Upregulation - Song Lin; Xin Li; Yi-Hua Chen; Feng Gao; Hao Chen; Neng-Yuan Hu; Lang Huang; Zheng-Yi Luo; Ji-Hong Liu; Qiang-Long You; Ya-Nan Yin; Ze-Lin Li; et al. (Molecular Neurobiology, 2018)

Surface IgM λ light chain is involved in the binding and infection of infectious bursal disease virus (IBDV) to DT40 cells - Jiaqi Chi; Leiming You; Peipei Li; Man Teng; Gaiping Zhang; Jun Luo; Aiping Wang (Virus Genes, 2018)

Forecasting industrial water demand in Huaihe River Basin due to environmental changes - Xiao-jun Wang; Jian-yun Zhang; Shamsuddin Shahid; Shou-hai Bi; Amgad Elmahdi; Chuan-hua Liao; You-de Li (Mitigation and Adaptation Strategies for Global Change, 2018)

Cloning and characterization of Agp1, the gene encoding the small subunit of ADP-glucose pyrophosphorylase from wheat and its relatives - Xiao-Wei Zhang; Qing Wang; Ling-Ling Zhang; Xiao-Juan Zhong; Qian-Tao Jiang; Jian Ma; Peng-Fei Qi; Wei Li; Guo-Yue Chen; Xiu-Jin Lan; Mei Deng; Zhen-Xiang Lu; et al. (Biologia, 2017)

Synthesis and antiproliferative properties of novel naringenin derivatives - Su-You Liu; Jiang Zeng; Kun-Jian Peng; Li-Chao Zhang; Li-Jun Liu; Zhi-Yong Luo; Da-You Ma (Medicinal Chemistry Research, 2017)

Comparison of infrared canopy temperature in a rubber plantation and tropical rain forest - Qing-Hai Song; Yun Deng; Yi -Ping Zhang; Xiao-Bao Deng; You-Xing Lin; Li-Guo Zhou; Xue-Hai Fei; Li-Qing Sha; Yun-Tong Liu; Wen-Jun Zhou; Jin-Bo Gao (International Journal of Biometeorology, 2017)

The Gut Bacterial Community Composition of Wild Cervus albirostris (White-Lipped Deer) Detected by the 16S Ribosomal RNA Gene Sequencing - Jun-gang Li; Chuan-dong Wang; Zhong-hai Tang; Ying-qiu Guo; Tian-cai Zheng; Yue-zhong Li; Zhang-qiang You (Current Microbiology, 2017)

Repellence of the main components from the essential oil of Glycosmis lucida Wall. ex Huang against two stored product insects - Shan-Shan Guo; Wen-Juan Zhang; Kai Yang; Jun-Yu Liang; Chun-Xue You; Cheng-Fang Wang; Yin-Ping Li; Zhu-Feng Geng; Zhi-Wei Deng; Shu-Shan Du (Natural Product Research, 2017)

Umbilical cord-derived mesenchymal stem cell transplantation for treating elderly vascular dementia - Yan He; Xingfang Jin; Jun Wang; Mingyao Meng; Zongliu Hou; Weimeng Tian; You Li; Wenju Wang; Yunhong Wei; Yipeng Wang; Hongqiong Meng; Xuyang Lu; et al. (Cell and Tissue Banking, 2017)

Effects of soybean isoflavone on intestinal antioxidant capacity and cytokines in young piglets fed oxidized fish oil - Lin Huang; Xian-yong Ma; Zong-yong Jiang; You-jun Hu; Chun-tian Zheng; Xue-fen Yang; Li Wang; Kai-guo Gao (Journal of Zhejiang University-SCIENCE B, 2016)

Potential dual role of nuclear factor-kappa B in experimental subarachnoid hemorrhage-induced early brain injury in rabbits - Wanchun You; Gang Zuo; Haitao Shen; Xiaodi Tian; Haiying Li; Haiping Zhu; Jun Yin; Tiejun Zhang; Zhong Wang (Inflammation Research, 2016)

Earth Fissures in Su–Xi–Chang Region, Jiangsu, China - Guang-ya Wang; Greg You; Jin-qi Zhu; Jun Yu; Wei Li (Surveys in Geophysics, 2016)

The PI3K/Akt/mTOR pathway regulates the replicative senescence of human VSMCs - Pan Tan; Yan-Jiao Wang; Shuang Li; Yi Wang; Je-Yu He; Yi-Yin Chen; Hui-Qian Deng; Wu Huang; Jun-Kun Zhan; You-Shuo Liu (Molecular and Cellular Biochemistry, 2016)

Impacts of CuO nanoparticles on nitrogen removal in sequencing batch biofilm reactors after short-term and long-term exposure and the functions of natural organic matter - Jun Hou; Guoxiang You; Yi Xu; Chao Wang; Peifang Wang; Lingzhan Miao; Yanhui Ao; Yi Li; Bowen LV; Yangyang Yang (Environmental Science and Pollution Research, 2016)

G2 rotavirus within an emergent VP7 evolutionary lineage circulating in children with acute diarrhea in Guangxi Province of China, 2014 - Hui Jin Dong; Yuan Qian; You Zhang; Lin Qing Zhao; Ru Nan Zhu; Yi Nong; Zhao Jun Mo; Rong Cheng Li (Archives of Virology, 2016)

Effect of alginate on the aggregation kinetics of copper oxide nanoparticles (CuO NPs): bridging interaction and hetero-aggregation induced by Ca2+ - Lingzhan Miao; Chao Wang; Jun Hou; Peifang Wang; Yanhui Ao; Yi Li; Bowen Lv; Yangyang Yang; Guoxiang You; Yi Xu (Environmental Science and Pollution Research, 2016)

Seismic dynamic monitoring in CO2 flooding based on characterization of frequency-dependent velocity factor - Jun-Hua Zhang; Jun Li; Wen Xiao; Ming-You Tan; Yun-Ying Zhang; Shi-Ling Cui; Zhi-Peng Qu (Applied Geophysics, 2016)

Functional polymorphisms in the gene encoding macrophage migration inhibitory factor (MIF) are associated with active pulmonary tuberculosis - Shou-Gang Kuai; Qin-Fang Ou; De-Hong You; Zhong-Bo Shang; Jun Wang; Jun Liu; Xi-Ke Zhou; Hao Pei; Li-Hua Huang (Infectious Diseases, 2016)

QTL mapping of flag leaf traits in common wheat using an integrated high-density SSR and SNP genetic linkage map - Qiuhong Wu; Yongxing Chen; Lin Fu; Shenghui Zhou; Jiaojiao Chen; Xiaojie Zhao; Dong Zhang; Shuhong Ouyang; Zhenzhong Wang; Dan Li; Guoxin Wang; Deyun Zhang; et al. (Euphytica, 2016)

Vascular endothelial growth factor-C protects heart from ischemia/reperfusion injury by inhibiting cardiomyocyte apoptosis - Xu-guang Chen; Yan-xia Lv; Dan Zhao; Lei Zhang; Fei Zheng; Jian-Ye Yang; Xiao-lin Li; Lu Wang; Lin-Yun Guo; Ya-mu Pan; Yu-wen Yan; Shi-You Chen; et al. (Molecular and Cellular Biochemistry, 2016)

Location- and Subunit-Specific NMDA Receptors Determine the Developmental Sevoflurane Neurotoxicity Through ERK1/2 Signaling - Wen-Yuan Wang; Li-Jie Jia; Yan Luo; Hong-Hai Zhang; Fang Cai; Hui Mao; Wei-Cai Xu; Jun-Biao Fang; Zhi-You Peng; Zheng-Wen Ma; Yan-Hong Chen; Juan Zhang; et al. (Molecular Neurobiology, 2016)

Transcriptome analysis reveals the potential contribution of long noncoding RNAs to brown adipocyte differentiation - Liang hui You; Li jun Zhu; Lei Yang; Chun mei Shi; Ling xia Pang; Jun Zhang; Xian wei Cui; Chen bo Ji; Xi rong Guo (Molecular Genetics and Genomics, 2015)

Construction of cDNA library from Prunus campanulata leaves and preliminary expressed sequence tag (EST) analysis during cold stress - Ying-Hui Zhang; Jun-Dong Rong; Li-Guang Chen; Ling-Yan Chen; Tian-You He; Yu-Shan Zheng (Biologia, 2015)

Correlation analysis of gene polymorphisms and β-lactam allergy - Jing Li; Xin-yue Liu; Lin-jing Li; Chong-ge You; Lei Shi; Shang-di Zhang; Qian Liu; Jun Wang; Ze-jing Liu; Ting-hong Lv (Journal of Zhejiang University-SCIENCE B, 2015)

MiR-1224-5p acts as a tumor suppressor by targeting CREB1 in malignant gliomas - Jin Qian; Rui Li; Ying-Yi Wang; Yan Shi; Wen-Kang Luan; Tao Tao; Jun-Xia Zhang; Yi-Chang Xu; Yong-Ping You (Molecular and Cellular Biochemistry, 2015)

Anxiolytic effects of ketamine in animal models of posttraumatic stress disorder - Li-Ming Zhang; Wen-Wen Zhou; Ya-Jun Ji; Ying Li; Nan Zhao; Hong-Xia Chen; Rui Xue; Xin-Guo Mei; You-Zhi Zhang; Heng-Lin Wang; Yun-Feng Li (Psychopharmacology, 2015)

Comparison of chemical, electrical, and combined activation methods for in vitro matured porcine oocytes - Shuai Liu; Kuiqing Cui; Hong Li Li; Jun Ming Sun; Xing Rong Lu; Kai Yuan Shen; Qing You Liu; De Shun Shi (In Vitro Cellular & Developmental Biology - Animal, 2015)

A down-regulated epi-allele of the genomes uncoupled 4 gene generates a xantha marker trait in rice - Rui-Qing Li; Jian-Zhong Huang; Hai-Jun Zhao; Hao-Wei Fu; You-Fa Li; Guo-Zhen Liu; Qing-Yao Shu (Theoretical and Applied Genetics, 2014)

Two Chinese pedigrees for adenomatous polyposis coli: new mutations at codon 1309 and predisposition to phenotypic variations - Dai-Xiang Liao; Bing Li; Xue-Mei Du; Jun-Hui Yu; Hong Chang; Zhi-Qiang Wu; Hao-Jie Hao; You-Xin Wang; Wei-Dong Han; Shu-jun Cheng; Cheng-Hua Luo (Familial Cancer, 2014)

Fine mapping of a dominant thermo-sensitive genic male sterility gene (BntsMs) in rapeseed (Brassica napus) with AFLP- and Brassica rapa-derived PCR markers - Xinhua Zeng; Wenpin Li; Yuhuan Wu; Fang Liu; Junling Luo; Yinglong Cao; Li Zhu; Yunjing Li; Jun Li; Qingbo You; Gang Wu (Theoretical and Applied Genetics, 2014)

Evaluation of geographic distribution of high-molecular-weight glutenin subunits (HMW-GS) in wild and cultivated Triticum species - Wei Li; Yu-Ming Wei; Li-Li Xu; An-Jun Liu; Yu-Zhen Sheng; Zhi-En Pu; Guo-Yue Cheng; You-Liang Zheng (Genetic Resources and Crop Evolution, 2014)

Release Behaviour of Single Pellets and Internal Fine 3D Structural Features Co-define the In Vitro Drug Release Profile - Shuo Yang; Xianzhen Yin; Caifen Wang; Haiyan Li; You He; Tiqiao Xiao; Lixin Sun; Jiasheng Li; Peter York; Jun He; Jiwen Zhang (The AAPS Journal, 2014)

Cosuppression of RBCS3B in Arabidopsis leads to severe photoinhibition caused by ROS accumulation - Gao-Miao Zhan; Rong-Jun Li; Zhi-Yong Hu; Jing Liu; Lin-Bin Deng; Shi-You Lu; Wei Hua (Plant Cell Reports, 2014)

Prevalence of human papillomavirus infection in esophageal and cervical cancers in the high incidence area for the two diseases from 2007 to 2009 in Linzhou of Henan Province, Northern China - Hong Yan Liu; Sheng Li Zhou; Jian Wei Ku; Dong Yun Zhang; Bei Li; Xue Na Han; Zong Min Fan; Ji Li Cui; Hong Li Lin; Er Tao Guo; Xi Chen; Yuan Yuan; et al. (Archives of Virology, 2014)

Cloning and characterization of squalene synthase gene from Poria cocos and its up-regulation by methyl jasmonate - Jian-Rong Wang; Jun-Fang Lin; Li-Qiong Guo; Lin-Feng You; Xian-Lu Zeng; Jia-Ming Wen (World Journal of Microbiology and Biotechnology, 2014)

Insulin-like growth factor 1 opposes the effects of C-reactive protein on endothelial cell activation - Shao-Jun Liu; Yun Zhong; Xiang-Yu You; Wei-Hua Liu; Ai-Qun Li; Shi-Ming Liu (Molecular and Cellular Biochemistry, 2014)

Cysteine residues 87 and 320 in the amino terminal domain of NMDA receptor GluN2A govern its homodimerization but do not influence GluN2A/GluN1 heteromeric assembly - Xiao-Min Zhang; Xin-You Lv; Yang Tang; Li-Jun Zhu; Jian-Hong Luo (Neuroscience Bulletin, 2013)

Antioxidant response and histopathological changes in brain tissue of pigeon exposed to avermectin - Ming Li; Tian-Zi You; Wen-Jun Zhu; Jian-Ping Qu; Ci Liu; Bing Zhao; Shi-Wen Xu; Shu Li (Ecotoxicology, 2013)

Bacillus abyssalis sp. nov., isolated from a sediment of the South China Sea - Zhi-Qing You; Jie Li; Sheng Qin; Xin-Peng Tian; Fa-Zuo Wang; Si Zhang; Wen-Jun Li (Antonie van Leeuwenhoek, 2013)

Reduced expression of aquaporin 9 in tubal ectopic pregnancy - Yin Fen Ji; Li You Chen; Kai Hong Xu; Ji Fen Yao; Yi Fu Shi; Xue Jun Shanguan (Journal of Molecular Histology, 2013)

Investigation of transferability of BovineSNP50 BeadChip from cattle to water buffalo for genome wide association study - Jun Jing Wu; Li Jun Song; Fang Jie Wu; Xian Wei Liang; Bing Zhuang Yang; D. Claire Wathes; Geoff E. Pollott; Zhangrui Cheng; De Shun Shi; Qing You Liu; Li Guo Yang; Shu Jun Zhang (Molecular Biology Reports, 2013)

Exploring the effect of organic matter on the interactions between mineral particles and cations with Wien effect measurements - Yu-Jun Wang; Ling-Xiang Wang; Cheng-Bao Li; You-Bin Si; Dong-Mei Zhou (Journal of Soils and Sediments, 2013)

Effects of AM Inoculation and Organic Amendment, Alone or in Combination, on Growth, P Nutrition, and Heavy-Metal Uptake of Tobacco in Pb-Cd-Contaminated Soil - Fa Yuan Wang; Ling Wang; Zhao Yong Shi; You Jun Li; Zhi Mei Song (Journal of Plant Growth Regulation, 2012)

Discovery and profiling of novel and conserved microRNAs during flower development in Carya cathayensis via deep sequencing - Zheng Jia Wang; Jian Qin Huang; You Jun Huang; Zheng Li; Bing Song Zheng (Planta, 2012)

Spatial variation of bacterial community structure of the Northern South China Sea in relation to water chemistry - Juan Ling; Jun-De Dong; You-Shao Wang; Yan-Ying Zhang; Chao Deng; Li Lin; Mei-Lin Wu; Fu-Lin Sun (Ecotoxicology, 2012)

A study on marine region carrying capacity and eco-compensation - Caihua Ma; Kui You; Weiwei Ma; Jun Xie; Fengqi Li (Journal of Ocean University of China, 2012)

VEGF is essential for the growth and migration of human hepatocellular carcinoma cells - Lei Zhang; Jia-Ning Wang; Jun-Ming Tang; Xia Kong; Jian-Ye Yang; Fei Zheng; Ling-Yun Guo; Yong-Zhang Huang; Li Zhang; Lin Tian; Shu-Fen Cao; Chang-Hai Tuo; et al. (Molecular Biology Reports, 2012)

Dynamics and functions of CD4+CD25high regulatory T lymphocytes in Chinese rhesus macaques during the early stage of infection with SIVmac239 - Shao-You Li; Hou-Jun Xia; Zheng-Xi Dai; Gao-Hong Zhang; Bo Fan; Ming-Hua Li; Rui-Rui Wang; Yong-Tang Zheng (Archives of Virology, 2012)

Norcantharidin, a protective therapeutic agent in renal tubulointerstitial fibrosis - Ying Li; Yan Ge; Fu You Liu; You Ming Peng; Lin Sun; Jun Li; Qiong Chen; Yan Sun; Kun Ye (Molecular and Cellular Biochemistry, 2012)

A high-frequency cyclic secondary somatic embryogenesis system for Cyclamen persicum Mill - Cui Rong You; Ting Jun Fan; Xue Qin Gong; Fu Hua Bian; Li Kun Liang; Fu Ning Qu (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

The soybean GmbZIP1 transcription factor enhances multiple abiotic stress tolerances in transgenic plants - Shi-Qing Gao; Ming Chen; Zhao-Shi Xu; Chang-Ping Zhao; Liancheng Li; Hui-jun Xu; Yi-miao Tang; Xin Zhao; You-Zhi Ma (Plant Molecular Biology, 2011)

Minimally-invasive treatment of communicating hydrocephalus using a percutaneous lumboperitoneal shunt - Lu Jia; Zhong-xin Zhao; Chao You; Jia-gang Liu; Si-qing Huang; Min He; Pei-gang Ji; Jie Duan; Yi-jun Zeng; Guo-ping Li (Journal of Zhejiang University-SCIENCE B, 2011)

Acetylcholine prevents angiotensin II-induced oxidative stress and apoptosis in H9c2 cells - Jin-Jun Liu; Dong-Ling Li; Juan Zhou; Lei Sun; Ming Zhao; Shan-Shan Kong; You-Hua Wang; Xiao-Jiang Yu; Jun Zhou; Wei-Jin Zang (Apoptosis, 2011)

A hybrid promoter-containing vector for direct cloning and enhanced expression of PCR-amplified ORFs in mammalian cells - Lei-ming You; Jun Luo; Ai-ping Wang; Gai-ping Zhang; Hai-bo Weng; Ya-nan Guo; Yun-chao Liu; Qiao-mu Li; Man Teng (Molecular Biology Reports, 2010)

The interaction between interferon-induced protein with tetratricopeptide repeats-1 and eukaryotic elongation factor-1A - Hong-Tao Li; Yong-Ping Su; Tian-Min Cheng; Jian-Ming Xu; Jie Liao; Ji-Chuan Chen; Chang-You Ji; Guo-Ping Ai; Jun-Ping Wang (Molecular and Cellular Biochemistry, 2010)

Exercise benefits cardiovascular health in hyperlipidemia rats correlating with changes of the cardiac vagus nerve - You-Hua Wang; Hao Hu; Sheng-Peng Wang; Zhen-Jun Tian; Quan-Jiang Zhang; Qiu-Xia Li; You-You Li; Xiao-Jiang Yu; Lei Sun; Dong-Ling Li; Bing Jia; Bing-Hang Liu; et al. (European Journal of Applied Physiology, 2010)

Genetic characterization of asymmetric reciprocal hybridization between the flatfishes Paralichthys olivaceus and Paralichthys dentatus - Dongdong Xu; Feng You; Zhihao Wu; Jun Li; Jing Ni; Zhizhong Xiao; Peijun Zhang; Yongli Xu (Genetica, 2009)

Role of muscle spindle in weightlessness-induced amyotrophia and muscle pain - Umar Ali; Xiao-Li Fan; Hao-Jun You (Neuroscience Bulletin, 2009)

Phase I clinical trial on intracoronary administration of Ad-hHGF treating severe coronary artery disease - Zhi-Jian Yang; You-Rong Zhang; Bo Chen; Shu-Lan Zhang; En-Zhi Jia; Lian-Sheng Wang; Tie-Bing Zhu; Chun-Jian Li; Hui Wang; Jun Huang; Ke-Jiang Cao; Wen-Zhu Ma; et al. (Molecular Biology Reports, 2009)

Establishment of cell lines using a doxycycline-inducible gene expression system to regulate expression of hepatitis B virus X protein - Hong Tang; Li Liu; Feng-Jun Liu; En-Qiang Chen; Seishi Murakami; Yong Lin; Fang He; Tao-You Zhou; Fei-Jun Huang (Archives of Virology, 2009)

Halobacillus naozhouensis sp. nov., a moderately halophilic bacterium isolated from a sea anemone - Yi-Guang Chen; Zhi-Xiong Liu; Yu-Qin Zhang; You-Xiang Zhang; Shu-Kun Tang; Entomack Borrathybay; Wen-Jun Li; Xiao-Long Cui (Antonie van Leeuwenhoek, 2009)

Molecular cloning and characterization of twoBrassica napus TTG1 genes reveal genus-specific nucleotide preference, extreme protein-level conservation and fast divergence of organ-specificity - Jun Lu; Jia-Na Li; Bo Lei; San-Gen Wang; You-Rong Chai (Genes & Genomics, 2009)

Infectivity and propagation of attenuated infectious bursal disease virus in the chicken B-lymphocyte cell line DT40 - Jun Luo; Gai-Ping Zhang; Jian-Ming Fan; Man Teng; Lei-Ming You; Ling Zhou; Rui-Guang Deng; Xuan-Nian Wang; Yan-Yan Yang; Li Wang; Guang-Xu Xing; Na Cheng (Archives of Virology, 2009)

A cotton (Gossypium hirsutum) DRE-binding transcription factor gene, GhDREB, confers enhanced tolerance to drought, high salt, and freezing stresses in transgenic wheat - Shi-Qing Gao; Ming Chen; Lian-Qin Xia; Hui-Jun Xiu; Zhao-Shi Xu; Lian-Cheng Li; Chang-Ping Zhao; Xian-Guo Cheng; You-Zhi Ma (Plant Cell Reports, 2009)

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.

Cloning and characterization of phosphorus starvation inducible Brassica napus PURPLE ACID PHOSPHATASE 12 gene family, and imprinting of a recently evolved MITE-minisatellite twin structure - Kun Lu; You-Rong Chai; Kai Zhang; Rui Wang; Li Chen; Bo Lei; Jun Lu; Xin-Fu Xu; Jia-Na Li (Theoretical and Applied Genetics, 2008)

Minocycline attenuates cognitive impairment and restrains oxidative stress in the hippocampus of rats with chronic cerebral hypoperfusion - Zhi-You Cai; Yong Yan; Shan-Quan Sun; Jun Zhang; Liang-Guo HUANG; Ning Yan; Fang Wu; Jie-Ying Li (Neuroscience Bulletin, 2008)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Molecular relationships between type Asia 1 new strain from China and type O Panasia strains of foot-and-mouth-disease virus - Dong Li; You-Jun Shang; Zai-Xin Liu; Xiang-Tao Liu; Xue-Peng Cai (Virus Genes, 2007)

Methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms and the risk of primary Hepatocellular Carcinoma (HCC) in a Chinese population - Li-Na Mu; Wei Cao; Zuo-Feng Zhang; Lin Cai; Qing-Wu Jiang; Nai-Chieh You; Binh Yang Goldstein; Guo-Rong Wei; Chuan-Wei Chen; Qing-Yi Lu; Xue-Fu Zhou; Bao-Guo Ding; et al. (Cancer Causes & Control, 2007)

The symbiosis phenotype and expression patterns of five nodule-specific genes of Astragalus sinicus under ammonium and salt stress conditions - Da-Song Chen; You-Guo Li; Jun-Chu Zhou (Plant Cell Reports, 2007)

Molecular cloning of Brassica napus TRANSPARENT TESTA 2 gene family encoding potential MYB regulatory proteins of proanthocyanidin biosynthesis - Yun-Liang Wei; Jia-Na Li; Jun Lu; Zhang-Lin Tang; Dong-Chun Pu; You-Rong Chai (Molecular Biology Reports, 2007)

Effects of Cold Shock on Microtubule Organization and Cell Cycle in Gynogenetically Activated Eggs of Olive Flounder (Paralichthys olivaceus) - Xiang-Ping Zhu; Feng You; Pei-Jun Zhang; Yong-Li Xu; Jian-He Xu (Marine Biotechnology, 2006)

Thermal effects of building’s external surfaces in city - Yi-ping Zhang; Yun-ling He; Yu-hong Liu; You-xin Ma; You-rong Li; Jun-xia Dou (Chinese Geographical Science, 2004)